Dose-dependent hepatorenal genotoxicity induced by polyethylene microplastics: Evidence from comet assay and apoptotic pathway activation - Souzan Abdel-Zaher; Shaimaa M.M. Saleh; Mahmoud S. Mohamed; Alaa El-Din H. Sayed (Tissue and Cell, 2027)

Correction to: Rosuvastatin-Loaded Glycerosomes as a Neuroprotective Strategy Against Hyperlipidemia-Induced Brain Dysfunction: Development, Optimization, and in vivo Evaluation - Mahran Mohamed Abd El-Emam; Mohamed Ibrahim; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed; Maha S. Kilany; Amira Ebrahim Alsemeh; Rania Said Moawad; Mohamed Fouad Mansour (Journal of Pharmaceutical Innovation, 2027)

Nano-selenium mitigates lead nanoparticle-induced hеpatonеural toxicity and growth performance in quails: Oxidative stress, neurotransmitter and anti-inflammatory response modulation - Omnia I. Eleouny; Magda I. Abo-Samaha; Sahar F. Mahmoud; Hanan A. Ghoneim; Adel H. Saad; Yasser S. El-Sayed (Tissue and Cell, 2026)

Effect of using mannan-oligosaccharides and β-glucans as feed additives on growth, biochemical parameters, and immunity of Salmonella enterica serovar Enteritidis-challenged turkey - Shimaa A. Amer; Rehab I. Hamed; Gehan K. Saleh; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Rania M. Ibrahim; Nehal M. Nabil; Maram M. Tawakol; Momen M. Aladl; Walaa A. El-Sayed; Mohamed A. Mahmoud; et al. (Veterinary Research Communications, 2026)

Estimation of economic injury levels and action thresholds for the two-spotted spider mite, Tetranychus urticae Koch, on strawberry plants - Eman M. Abdelmaksoud; Shoukry A. El-Refai; Kadry W. Mahmoud; Walaa El-Sayed; Mohamed E. Ragab (Experimental and Applied Acarology, 2026)
Strawberry ( Fragaria × ananassa Duch.) is a high-value global crop, yet its productivity is severely constrained by the two-spotted spider mite, Tetranychus urticae Koch. Developing localized economic thresholds is a cornerstone of sustainable Integrated Pest Management (IPM) to mitigate yield losses and reduce acaricide reliance. This two-season field study (2019–2020) investigated the quantitative relationship between T. urticae population density and strawberry yield in Egypt. Using varying infestation levels established via Chitosan (Top9 0.1%) treatments, linear regression and Chi-square (χ 2 ) analyses were employed to determine four critical economic levels: General Equilibrium Position (GEP), Economic Threshold Level (ETL), Economic Injury Level (EIL), and Economic Damage Level (EDL). Results revealed a highly significant negative correlation between mite density and yield ( r = -0.96*** in 2019; r = -0.97*** in 2020), with an average yield reduction of 1.25% per mite. The estimated EIL and ETL were 4.0 mites/leaf in 2019 and 3.4 mites/leaf in 2020. These findings provide a precise decision-making framework for mite management in Mediterranean strawberry production. The low estimated thresholds suggest that proactive, preventive management strategies are more effective than reactive control to maintain strawberry yield.

Gamma Radiation–Induced Synthesis of Pectin/Arabic Gum-Based Nanocomposite Hydrogels for Enhanced Water Remediation - Asmaa Sayed; D. M. Aboelkhir; Razan Mohamed; Ayman Amin; Ghada A. Mahmoud (Water, Air, & Soil Pollution, 2026)

Surface Modification of PVDF Membranes with GA-Crosslinked GO/PVA for Enhanced Methylene Blue Rejection and Antifouling Performance - Mohamed Dawam; Fatma Mohamed El-Sayed; Mahmoud Y. Zorainy; Hussein Oraby; Mohamed Gobara (Water, Air, & Soil Pollution, 2026)

Rosemary (Rosmarinus officinalis) Extract Attenuates Methotrexate-Induced Oxidative Stress, Inflammatory Disturbance, and Apoptotic Lung Injury: A Molecular and Histopathological Study - Abd El Ghany A. Moustafa; Aly Fahmy Mohamed; Ibrahim M. Ibrahim Amr; Hassan Fathy Kaabo; Laila El-sayed El-moselhy; Tamer Albasyoni Gomah; Amer M. Abdel Hamid; Amal Mahmoud Hammad; Walid Mostafa Sayed Ahmed; Fawzy Mahmoud Abou Galala; Fayez Mohammed Abd Elfattah Elbayoumy; Mohamed E. Amer; et al. (Cell Biochemistry and Biophysics, 2026)

Plant-derived natural products against hepatocellular carcinoma: chemical diversity, mechanisms of action, and organ-based classification - Nourhan Hisham Shady; Aliaa Gamal; Asmaa Emad Fekry; Amna Mahmoud Sayed; Zaki Ebrahim Afify; Ziad Abdellah Mohamed; Ingy M. Hashad; Mohammed I. Rushdi; Ahmed Zayed; Usama Ramadan Abdelmohsen (Natural Product Research, 2026)

Development and validation of an interpretable EEG-based deep learning framework for estrus detection in dairy cows - Kang Hai; Yu Zhou; Jun Wang; Hui Wang; Waleid Mohamed EL-Sayed Shakweer; Shanshan Yin; Amal Mahmoud Aboelmaaty (Computers and Electronics in Agriculture, 2026)

Innovative green HPTLC strategy for the analysis of telmisartan–nebivolol combination used for hypertension control. Application to dosage form and biological fluids - Sayed M. Derayea; Mahmoud Abdelgaleel; Dalia M. Nagi; Ebtihal Samir (Sustainable Chemistry and Pharmacy, 2026)

Empagliflozin and naringenin mitigate cisplatin-induced testicular injury via modulating NLRP3 inflammasome-mediated pyroptosis: Integrated molecular docking and in vivo evidence - Sayed Mahmoud; Rasha H. Abdel-Ghany; Atef S. Elgharbawy; Tarek Khamis; Esraa M. Zakaria (Reproductive Toxicology, 2026)

Microalgae-based aquafeeds for penaeid shrimp: progress toward improved growth, immune modulation, and sustainable production - Samia Elbahnaswy; Eman Zahran; Mai A. M. El-Son; Amany M. Shosha; El-sayed H. Eissa; Mohamed AbdElrahman; Mohamed E. Abd El-Hack; Hanan H. Abdelhafeez; Mahmoud G. El Sebaei (Veterinary Research Communications, 2026)

Dietary yeast-derived nucleotides enhance reproductive efficiency, blood metabolic profile, antioxidant status, and immune function in rabbit does - Noura H. Gouda; Sameh A. Abdelnour; Elsayed S. I. Mohammed; Mohamed Shawky El Sayed; Mohamed Ashour; Roshmon Thomas Mathew; Mohammed Tariq Saud Albaloushi; Hailah M. Almohaimeed; Ehab El-Haroun; Mahmoud S. Abd-Allah (Veterinary Research Communications, 2026)

Type 2 Diabetes-Induced Molecular and Functional Impairment of Adipose Tissue-Derived Mesenchymal Stromal Cells (ASCs) and Interferon Gamma Priming for Enhanced Diabetic ASC-Based Therapy - Alaa Zeinhom; Ammar Y. Mohamed; Nahla N. Abdel-Aziz; Mostafa Sayed Diab; Amir M. H. Salem; Noha N. Yassen; Eman E. A. Mohammed; Amal M. Mohamed; Ola M. Eid; Shymaa H. Hussein; Marwa Farid; Engy K. Tharwat; et al. (Stem Cell Reviews and Reports, 2026)

Paclobutrazol-mediated improvement of brown spot resistance in rice seedlings under salinity stress conditions - Hossam S. El-Beltagi; Mohamed Fathi El-Nady; Adel A. Rezk; Abdelaziz M. Tahoon; Hosny Hamed Kesba; Elsayed Abd Elmaksoud Abomarzoka; Ahmed Mahmoud Ismail; Awad Mohamed El-Sayed; Wael Elmenofy; Metwaly Mahfouz Salem Metwaly (European Journal of Plant Pathology, 2026)

Effect of milling on natural radioactivity of Egyptian zircon sand: an assessment of alpha and beta radiation emissions - Kolthoum I. Othman; Ola Makld; Mahmoud A. Mosleh; M. El-Sayed Ali; S. El-Houte (Environmental Geochemistry and Health, 2026)
This study aims to investigate the effect of milling on the natural radioactivity of Egyptian zircon sand, focusing on the gross alpha (α) and goss beta (β) activity concentrations, with additional evaluation of calcination and sulfuric acid leaching. Zircon samples were milled for different durations, and their gross α and gross β activity concentrations were measured using an ATOMTEX AT1329 sample counter. The measurements showed that both gross α and gross β apparent activity concentrations increased with milling time, reaching maximum values of 3.5 ± 1.4 Bq/g and 7.2 ± 2.2 Bq/g, respectively, in the sample milled for 36 h. These values increased to 7.7 ± 3.1 Bq/g and 14.72 ± 4.4 Bq/g after calcination, while acid leaching resulted in a pronounced decrease in these values to 4.5 ± 1.7 Bq/g for alpha and 9.6 ± 2.9 Bq/g for beta. Milling reduces particle size and increases the escape probability of α and β particles from the sample bulk, while calcination removes the polyamide layer formed during milling, which acts as a barrier to particle detection. These findings highlight the potential radiation hazards associated with zircon sand processing to safeguard occupational health and environmental safety in industries working with this material.

Integrating remote sensing, geophysical and geochemical approach for targeting intrusion-associated hydrothermal gold deposits: insights from Northeastern Desert in Egypt - Mahmoud Abd El-Rahman Hegab; Yousef M. Youssef; Kareem Hamed Abd El–Wahid; Hanaa A. Megahed; Ahmed A. El-Sheikh; Sayed A. Mohamed; Hafsa M. Atia; Heba El-Bagoury; El Sayed A. Saber (Advances in Space Research, 2026)

From waste to worth: A bio-inspired green route for the fabrication of yucca leaf–TiO2 nanocomposites toward efficient and sustainable water purification - Sayed Kotb Ali; Mostafa M. Emara; Rabie Saad Farag; Moaz M. Abdou; Mahmoud F. Mubarak (Environmental Nanotechnology, Monitoring & Management, 2026)

Bacillus -based probiotic supplementation effect on performance, bone health, and meat quality of Muscovy ducks - Ahmed Mohammed; Manal Mahmoud; Sherief Sayed; Doaa Abd El-Maguid; Nadim Amarin; Eman Negm (Tropical Animal Health and Production, 2026)

Genetic Diversity Analysis Using Start Codon Targeted (SCoT) and Sequence-Related Amplified Polymorphism (SRAP) Markers and Some Leaf Anatomical Traits in Sixteen Rutaceae Taxa - Mohamed A. Abdein; Samah O. Osman; Amr M. M. Mahmoud; Sahar A. M. Shamseldin; Mai M. Wahba; Sayed Y. Mohamed; Emadeldin A. H. Ahmed; Salwa El-Habashy; Rania A. E. Abdelzaher; Noha A. Sukar; Amany M. Mousa; Amal Ahmed Alyamani; et al. (Plant Molecular Biology Reporter, 2026)

Shifting Cassia javanica Cultivation From Shallow to In-hole Systems Maintains Microbial Activity and Plant Cover in the Urban Landscapes - Mahmoud O. Hassan; Mohamed Al-zharani; Wesal S. Tanko; Bader Z. Albogami; Yehia Hazzazi; Lina M. Alneghery; Fahd A. Nasr; Amany A. H. Abeed; Howida Y. Mohamed; Maha H. Khalaf; Khaled N. M. El-Sayed (Journal of Soil Science and Plant Nutrition, 2026)

Biosynthesis of Magnetite Nanoparticles and its Impact on Productivity and Biochemical Components of Chili Pepper Under Saline Conditions - Mansour E. Ramadan; Mahmoud M. El-Saber; Ahmed E. Abdelhamid; Ahmed A. El-Sayed (Agricultural Research, 2026)

Comparative analysis of the morphological heterogeneity of smooth muscle cells in two avian species: the muscovy Duck (Cairina moschata) and the Japanese quail (Coturnix japonica): ultrastructural and histochemical study - Hanan H. Abd-Elhafeez; Alaa Sayed Abou-Elhamd; Basma Mohamed Kamal; Hesham Ismail; Sherief M. Abdel-Raheem; Mahmoud H. A. Mohamed; Ahmed M. A. Meligy; Soha A. Soliman (Protoplasma, 2026)

Nano-selenium ameliorates lead oxide nanoparticle-induced reproductive toxicity in japanese quails via restoring gonadal antioxidant activity and normalization of sex hormones - Omnia I. Eleouny; Magda I. Abo-Samaha; Hanan A. Ghoneim; Sahar F. Mahmoud; Adel H. Saad; Yasser S. El-Sayed (Tissue and Cell, 2026)

Geological mapping of Neoproterozoic rocks in Zug El-Bohar area, NW Red Sea rift system, Egypt: an integrated hyperspectral remote sensing, petrographic, and geochemical approach - Farouk Sayed; Aya S. Shereif; Ali Shebl; Árpád Csámer; Abdelhalim S. Mahmoud (Remote Sensing Applications: Society and Environment, 2026)

Structurally-controlled radioactive and rare metal mineralizations associated with potassic alteration in Umm Ara granitoids, southern Eastern Desert, Egypt: Implications from remote sensing, whole-rock chemistry, and geophysical data - Adel Fathy; Mokhles K. Azer; Abdelhalim S. Mahmoud; Farouk Sayed; Ahmed A. Masoud; Faris A. Abanumay (Journal of Geochemical Exploration, 2026)

Highly sensitive colorimetric 3D covalent organic framework sensors with artificial intelligence analysis enabled early detection of plant diseases - Asmaa Gbiliy; Ibrahim Senosy; Marwa A.A. Saadan; Mahmoud Sayed; I.P.W.A.V. Kumara; Ge-Fei Hao; Man-Qun Wang (Chemical Engineering Journal, 2026)

Melatonin supplementation alleviates stocking-density stress and enhances growth, immune, and physiological performance of Sparus aurata cultured in groundwater-based systems - Ashraf. I.G. Elhetawy; Mohamed M. Abdel-Rahim; Salma Mahmoud Zeid; Omar M. El-Daly; Tamer El-Sayed Ali (Veterinary Research Communications, 2026)
The intensive mariculture of S. aurata can promote aquaculture development, although it can also pose challenges because of predatory behavior and environmental stressors caused by intensification. The objective of this study is to alleviate stress and prevent cannibalism, thereby improving the fish’s performance and welfare. A 90-day growth experiment investigated the dietary inclusion of melatonin (ML) on Sparus aurata performance, physiology, immunity, histopathology, and welfare when grown in saline groundwater (36 ppt) at stocking densities (SD) of 50 fish/500 L‒tank (SD 50 ) and 100 fish/500 L‒tank (SD 100 ). Six fish groups in triplicate were fed three increasing levels of ML (0, 25, and 50 mg/kg − 1 diet) expressed as T1, T2 and T3 under SD 50 , and T4, T5, and T6 under SD 100 . Fish ( n = 1350) weighing 16.46 ± 0.18 g/fish were grown using a flow-through system and a daily feeding rate of 4%. The results revealed significant declines in nitrogen by-product (NH 3 and NO 2 ) levels of fish fed ML in a dose density-dependent manner. Fish fed ML under both densities showed significantly improved growth indices, FCR, growth hormone, and crude protein content compared with those fed the control diet, with T2 and T6 groups achieving the highest values. ML augmentation enhanced serum lipase, protease, immunoglobulin, albumin, globulin, antioxidants, and proinflammatory cytokine interleukin-1β and lowered serum cortisol, glucose, ALT, AST, and ALP. Under both densities, the ML-fish presented healthier livers and intestines than those fed the control diet, which showed marked liver vacuoles and steatotic changes. The ML-SD interaction showed superior fish performance, particularly in groups T2 and T6; thus, it is recommended to administer dietary melatonin at 25 mg/kg for seabream reared at 50 fish per 500-liter tank and 50 mg/kg for those cultivated at 100 fish per 500-liter tank using groundwater.

Rosuvastatin-Loaded Glycerosomes as a Neuroprotective Strategy Against Hyperlipidemia-Induced Brain Dysfunction: Development, Optimization, and in vivo Evaluation - Mahran Mohamed Abd El-Emam; Mohamed Ibrahim; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed; Maha S. Kilany; Amira Ebrahim Alsemeh; Rania Said Moawad; Mohamed Fouad Mansour (Journal of Pharmaceutical Innovation, 2026)
Objective Brain injury and neurodegenerative conditions are largely caused by oxidative damage and endoplasmic reticulum (ER) stress spurred on by hyperlipidemia. To lessen these consequences in the brains of hyperlipidemic rats, this study assesses the therapeutic potential of both rosuvastatin glycerosomes (RSV GLSMs) and niacin. Methods The study had five groups: control, hyperlipidemia induced by poloxamer 407 (P407), RSV GLSMs, niacin, or a combination of RSV GLSMs and niacin. Serum samples were collected for lipid profile assessment, whereas brain tissues were harvested for Reverse Transcription Polymerase Chain Reaction, histopathological, and immunohistochemical analyses. Results The treatment of P407 significantly decreased high-density lipoprotein and increased serum triglycerides, although RSV GLSMs and niacin substantially mitigated these changes. Malondialdehyde also surged in P407 rats, and total antioxidant capacity was diminished. RSV GLSMs and niacin supplementation significantly improved antioxidative defenses, with the combination therapy exhibiting more pronounced effects. RSV GLSMs and niacin notably lessen ER stress–responsive gene expression, including Eukaryotic Initiation Factor 2 alpha (eIF2α), C/EBP Homologous Protein (CHOP), X-box Binding Protein 1 (XBP1), c-Jun N-terminal Kinase (JNK), Binding Immunoglobulin Protein (BIP), and Activating Transcription Factor 6 (ATF-6) levels. In addition, RSV GLSMs and niacin improved autophagy by downregulating the Mammalian Target of Rapamycin (mTOR) and p62, and upregulating Beclin1 and Microtubule-associated protein 1A/1B-light chain 3, type II (LC3-II). According to immunohistochemical findings, RSV GLSMs and niacin reduced reactive gliosis and modulated the expression of B-cell lymphoma 2/Bcl-2-associated X protein (Bcl-2/Bax). Histopathological findings exhibited improved brain morphology, reduced vacuolization, and normalized glial cell distribution in the RSV GLSMs and niacin combination group, closely resembling the control group. Conclusions Overall, RSV GLSMs and niacin effectively mitigate hyperlipidemia-induced brain damage by modulating oxidative stress, ER stress, and autophagy pathways, suggesting potential as a promising treatment strategy.

Failure Mechanisms of Helical Piles and Evaluation of Capacity Prediction Models - Nader Ibrahim; Sayed M. Ahmed; Mahmoud S. Hammad (Geotechnical and Geological Engineering, 2026)

Nutritional intervention with glycyrrhetinic acid (GA) enhances growth and metabolic balance in channel catfish (Ictalurus punctatus) fed a high-fat diet - Hesham Eed Desouky; Guang-zhen Jiang; Kenneth Prudence Abasubong; Nouran Mahmoud Sayed; Michael Chukwuemeka Umehai; Jean-Jacques Y. Adjoumani; Wen-bin Liu (Fish Physiology and Biochemistry, 2026)

Nano-curcumin mitigates aluminum oxide nanoparticle toxicity in Nile tilapia through antioxidant and immune modulation - Sahr B. Mahmoud; Maha M. Rashad; Ghada E. Ali; Eman Ragab; Omaima Ahmed; Fady Sayed Youssef; Ola Hasan Abd El Megeed (Fish Physiology and Biochemistry, 2026)
Our study investigated the toxicological effects of aluminum oxide nanoparticles (Al 2 O 3 -NPs) and the potential protective role of dietary nano-curcumin (N-CUR) in juvenile Oreochromis niloticus (30.39 ± 0.05 g) under controlled experimental conditions. It was hypothesized that N-CUR could mitigate the adverse impacts of Al 2 O 3 -NPs on growth, biochemical, oxidative, and histopathological parameters. A total of 180 O. niloticus were divided into six groups: a control group, two N-CUR-supplemented diets (40 and 50 mg/kg), an Al 2 O 3 -NP-exposed group (10 mg/L), and two co-treated groups receiving both treatments for 4 weeks. Growth performance, biochemical, immunological, antioxidant, and histopathological parameters were assessed. Exposure to Al 2 O 3 -NPs markedly reduced growth indices and survivability while elevating ALT activity and pro-inflammatory gene expression (TNFα, IL1β, MT). Antioxidant genes (CAT and SOD) were significantly downregulated, and histopathological lesions, including hyperemia, hyperplasia, and vacuolization, were evident. Conversely, N-CUR co-supplementation significantly improved growth (14.5%–46.1%), feed efficiency (46.7%–74.1%), and specific growth rate (219%–605%). It also reduced ALT (37.7%–40.1%) and enhanced albumin, A/G ratio, and IgM levels ( P < 0.05). Overall, these findings indicate that dietary N-CUR attenuated Al 2 O 3 -NP-induced oxidative and inflammatory stress, thereby improving the biochemical and histological health of O. niloticus . Hence, these outcomes provide a mechanistic proof of dietary N-CUR’s protective role against toxicity induced by Al 2 O 3 -NPs, indicating the need for further investigation in exposure scenarios that are relevant to the environment.

Infection control and wound care innovations in plastic surgery: a multidisciplinary approach - Rasha Abu-Khudir; Ahmed S. Doghish; Reda M. Mansour; Ghadir A. Sayed; Nourhan H. Elshami; Hebatallah Ahmed Mohamed Moustafa; Wagiha S. Elkalla; Ahmed O. Abdulkader; Sherif S. Abdel Mageed; Osama A. Mohammed; Rabab S. Hamad; Ahmed I. Abulsoud; et al. (Folia Microbiologica, 2026)

Impact of different weaning strategies on growth indices, biochemical composition, and digestive enzyme activity in Stellate sturgeon (Acipenser stellatus) larvae - Alinaghi Sarpanah; Zabihollah Pajand; Soheil Yousefi; Mir Hamed Sayed Hassani; Ayoub Yousefi Jourdehi; Reza Ghorbani Vaghei; Mahmoud Mohseni; Younes Golalipour; Omid Hashemi; Maryam Monsef Shokri; Tooraj Sohrabi (Animal Feed Science and Technology, 2026)

Solar-powered agricultural robots: a systematic review of technological synergies, sustainability impacts, and future pathways for autonomous farming - Hassan A.A. Sayed; Qinghui Lai; Jielei Tu; Mahmoud A. Abdelhamid; Tarek Kh. Abdelkader; T.M. Tawfik; Rasheed Olalekan Olajide; Misbah Uddin; Mohamed Refai (Computers and Electronics in Agriculture, 2026)

Integrating hydrogeochemical analysis and machine learning to assess surface–groundwater interactions in an arid basin (Middle Egypt) - Ahmed A. Abdelhady; Mamdouh S. Morsi; Nouria E.A. Aboshaala; Mahmoud M. Khalil; Hadi M. Elshourbagi; Esam Ismail; Esam El Sayed; Ashraf M.T. Elewa; Emad Youssef; Basma A.A. Balboul (Journal of African Earth Sciences, 2026)

Evaluation of free rosmarinic acid and rosmarinic acid-loaded chitosan nanoparticles in buffalo sperm cryopreservation: Impacts on sperm quality, functionality, and fertility potential - Fatma Mohsen Shalaby; Ohoud Ali Saeed Alghamdi; Ali Ali El-Raghi; Mahmoud A.E. Hassan; Walaa M. Essawi; Amany Omar Elrefaie; Amal El-Sayed Abd El Hady; Kandil Abd El Hai Attia (Cryobiology, 2026)

Energy and environmental impacts of wheat production: a comparative study of diesel and photovoltaic irrigation systems - Mahmoud A. Abdelhamid; Hassan A. A. Sayed; Tarek Kh. Abdelkader; Fatma M. Shaaban; Ashrf A. Anwer; Mohamed A. Refai (Environment, Development and Sustainability, 2026)
Increasing energy demand and environmental concerns have led to interest in renewable energy for agricultural irrigation to promote sustainable agriculture. Therefore, this research aims to assess and compare the environmental impacts and energy of wheat production in Egypt under diesel-driven (Sc-I) and solar PV-driven (Sc-II) irrigation systems. The data was collected from 181 wheat farms during the 2022–2023 season. The environmental assessment was conducted using a life cycle methodology from cradle to farm gate, and one kg of harvested wheat grains was used as the functional unit. The results showed that total energy inputs reached 108,506.97 MJ ha − 1 for Sc-I and 38,480.04 MJ ha − 1 for Sc-II, whereas the corresponding energy outputs were 153,735.55 and 144,192.30 MJ ha − 1 , respectively. Among the energy sources used for Sc-I, fuel for the irrigation system accounted for 63.2%, followed by fertilizer (17.3%). On the other hand, total fertilizer has the largest share in Sc-II (44.7%), followed by water (24%). Moreover, Sc-II led to a 64.5% reduction in total energy input. The global warming potential is estimated at 1.09 kg CO₂-eq kg − 1 for Sc-I and 0.19 kg CO₂-eq kg − 1 for Sc-II. Sc-II resulted in lower impacts across most environmental categories; however, slight increases were observed in abiotic depletion and freshwater aquatic ecotoxicity compared with Sc-I. While for agricultural operations, Sc-II led to a reduction in all environmental impact categories. Furthermore, solar PV-powered irrigation systems can substantially reduce energy consumption and emissions, providing a practical pathway towards sustainable agricultural production.

Effect of irradiated and unirradiated Calotropis procera (R.Br.) (Asclepiadaceae) leaves extract on Culex pipiens larvae (Diptera, Culicidae) - Tammy Samir El sayed; Salwa Abdou Rizk; Rehab Mahmoud Sayed (International Journal of Tropical Insect Science, 2026)

Epidemiology and immunoprophylaxis of lactococcosis in European Sea bass (Dicentrarchus labrax): A comprehensive study from Egyptian Aquaculture - Talal A.M. bo Selema; Riad H. Khalil; Mahmoud M. Abotaleb; El-Sayed Hemdan Eissa; Mohamed Fathi (The Veterinary Journal, 2026)

Optimization of Beet Thick Juice Storage: Impact of Storage Conditions on the Rheological Behavior - Marwa Abdelhak; El-Sayed A. Abdel-Rahman; Adel A. Abdellah; Mohamed M. Abd El-Wahab; Mahmoud N. Abdelmoez (Sugar Tech, 2026)
Establishing a manufacturing period for concentrated beet juice is a promising strategy to increase the productivity of white sugar and address climatic variability. Key parameters including temperature and stabilization treatments are crucial to optimizing the storage process at a reasonable cost. To this end, a pilot-scale plant was built with 12 tanks, three levels of storage temperatures (15, 25, and 35 °C), and three disinfection treatments. A rheological evaluation, during six months of storage, was investigated in relation to physiochemical and microbiological changes. The rheological behavior fits well with the power law model at different test temperatures of 25, 55 and 85 °C. The data demonstrated that thick juice is non-Newtonian fluid, displaying dilatant trend (1.0 < flow index ( n ) < 1.15) at low temperature of 25 $$^°$$ ∘ C and pseudoplastic (0.7 < n < 0.99) at higher temperatures of 55 and 85 $$^°$$ ∘ C. The consistency coefficient showed a temperature-dependent decline, with activation energy (E a ) values ranging from 17.18 to 29.57 kJ/mol. At a constant shear rate of 50 s −1 , apparent viscosity remained stable before and after storage across most treatments, except for a significant decrease observed in the untreated sample at 35 °C due to microbial deterioration. The findings highlight the off-season potential for sugar production and demonstrate that under optimal storage conditions, thick juice can be preserved in hot climates for a prolonged duration without degradation or significant impact on rheological behavior.

Potato Irrigation Suitability Assessment via Ninja Optimization Algorithm-Tuned RegNet on Physicochemical Quality Data - Sayed Elkenawy; Ebrahim A. Mattar; Amel Ali Alhussan; Mahmoud Shabrawy; Marwa M. Eid; Mohamed E. Ghoneim (Potato Research, 2026)

A self-organized fuzzy neural model for the pressurizer system in nuclear power plants - Elsayed H. Ali; Amal A. Sheta; Sayed M. El-Araby; Mohammed I. Mahmoud; Tarek A. Mahmoud (Annals of Nuclear Energy, 2026)

Nanocapsule-based vitamin B12 as a novel strategy against vancomycin-induced nephrotoxicity: Targeting oxidative stress, ER stress, inflammation, and fibrosis in rats - Mahran Mohamed Abd El-Emam; Maha S. Kilany; Mohamed Ibrahim; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed; Tarek khamis; Rasha Ahmed Ahmed Agaga; Asmaa Monir Eltaweel; Mohamed Fouad Mansour (Toxicology and Applied Pharmacology, 2026)

Remote sensing and geological characterization of the polydeformed Atud Basin and surrounding rocks, Eastern Desert, Egypt - Sayed M. Sayed; Safinaz A.A. Mahmoud; Reda Abdu Yousef El-Qassas; Amin Esmail Khalil; Yahia A. El Kazzaz (Journal of African Earth Sciences, 2026)

Oil sludge from an environmentally hazardous pollutant to an efficient source for energy production via thermal/ catalytic pyrolysis routes - Mohamed N.A. Mahmoud; Esraa M. El-Fawal; Ahmed M.A. El Naggar; Asmaa I. Zahran; Hussien A. El Sayed; Islam M. El-Sewify; Bassem H. Heakal; Mostafa M.H. Khalil (Fuel, 2026)

A comprehensive review of the developments in the electroanalytical methods for the detection of illegal food colorants in food and spices - Marwa El Badry Mohamed; Ahmed Sheriff Mohamed; Soryal Fathi Shaker; Mai Eid Matrawy; Mahmoud Mohamed Sayed; Noha Badr Elrabeiy (Food Chemistry, 2026)

New insights into the potential effects of date palm seed powder supplementation on the growth, hemato-biochemical indices, organ histology, and gene expression in Rahmani sheep - Hesham S. Ghazzawy; Nashi K. Alqahtani; Roshmon Thomas Mathew; Hassan M. Ali-Dinar; Osama H. Mahmoud Hassan; Hebatallah M. Saad; Yasmin M. Abd El-Aziz; Ehab El-Haroun; Moaheda E.H. Eissa; El-Sayed Hemdan Eissa (Tropical Animal Health and Production, 2026)

Amelioration of intestinal ischemia reperfusion injury by diacerein via regulation of inflammasome/caspase-1/IL-1β and Wnt/β-catenin pathways in juvenile rats - Marwa Monier Mahmoud Refaie; Nada Amgad Mohamed Abdel Majeed; Sayed Shehata; Asmaa A. Muhammed; Salma M. Hassan; Hoda S. Sherkawy; Fatma F. Ali; Mohamed Rabie Saad; Mousa Mohsen; Shereen Mohammed Mohammed Elsaghir; Enas Fathy; Olivia N. Beshay (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Intestinal ischemia reperfusion (II/R) is an abdominal critical case especially in neonates and during childhood affecting not only the intestinal tissue but also it could damage other remote organs including cardiac tissue even following surgical intervention. Immune homeostasis during II/R has a major role in controlling its progression. Thus, finding additive medical treatment besides the surgical one becomes an urgent need to keep the tissue. So that, we aimed to evaluate the possible ameliorative effect of diacerein (DIA) on II/R-induced injury in juvenile rats. Forty juvenile rats of Wistar albino species were randomly allocated into four different groups: sham group, DIA given group, II/R group via clamping superior mesenteric artery, DIA-treated group (50 mg/kg) with induction of II/R. Data of current model revealed a significant elevation of the measured cardiac enzymes, cleaved caspase-3, and nuclear factor kappa β (NF-κB) in the untreated ischemic group with disturbed oxidative stress parameters, accompanied with dysregulation of inflammasome/caspase-1/IL-1β and Wnt/β-catenin signaling cascades. Fortunately, upon co-administration of DIA, there is a significant decrease of cardiac enzymes, cleaved caspase-3, and NF-κB with normalization of oxidative stress parameters and regulation of inflammasome/caspase-1/IL-1β and Wnt/β-catenin pathways confirmed by marked mitigation of the histopathological changes. This effect of DIA is greatly attributed to its pharmacological properties including IL-1β antagonist effect, anti-oxidant, anti-apoptotic, and anti-inflammatory properties. Thus, DIA could be considered as an adjuvant future medical therapy for those cases of II/R. Graphical abstract

Molecular mechanisms underlying cyclophosphamide-induced ovarian injury and protective strategies - Ehab E. Sharata; Taha Bakry; Habiba Gamal Atta; Habiba Atef Mohammed; Nazema Shaker Diab; Rofaida Ashraf Atef; Roaa Sayed Hosney; Mahmoud Mohamed Omar; Ramadan A. M. Hemeida (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Cyclophosphamide (CP) is an anti-cancer medication that also treats chronic inflammatory illnesses caused by the immune system. Although CP is widely used, it can occasionally have limited therapeutic efficacy due to its significant combined toxicities. Ovarian damage caused by CP is a major problem for patients, and premature ovarian failure (POF) is a serious side effect of CP that commonly affects female patients. Mechanistic investigations have implicated oxidative stress, inflammatory responses, and apoptosis as critical components in the etiology of CP-induced POF, although the exact process by which this ovarian toxicity occurs remains unclear. After CP causes ovarian cells to generate proinflammatory cytokines, including interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), nuclear factor kappa B (NF-κB) is activated. The activation of the NLRP3 inflammasome is the subsequent stage. In addition, Nrf2/HO-1 has been identified as an important signaling pathway that mitigates oxidative stress in CP-induced POF due to its anti-inflammatory and antioxidative characteristics. Moreover, several recent studies highlighted the role of α-klotho deficiency in ovarian aging. Quercetin, resveratrol, berberine, curcumin, irbesartan, mirtazapine, sildenafil, atorvastatin, donepezil, cilostazol, moxibustion, LCZ696, buspirone, levomilnacipran, melatonin, diosmin, and azilsartan are some of the agents that may protect against ovarian injury caused by CP, as shown in Graphical abstract. Our goal in writing this study is to provide a concise overview of the possible redox molecular pathways that cause ovarian harm in CP and how to potentially ameliorate them. Finally, investigation into these molecular pathways may pave the way for early ovarian damage relief and for the development of different agent strategies to alleviate CP-mediated POF. Graphical Abstract

Tranexamic acid for spontaneous intracerebral hemorrhage: hematoma control without clinical benefits? A meta-analysis of RCTs - Mahmoud M. Elhady; Eslam Mohammed Rabea; Samah Bahy Mohammed Ebaed; Manar Adel; Moustafa Z. Elattar; Mahmoud Eleisawy; Ahmed A. Lashin; Ahmed A. Elfeky; Mohamed Hesham Gamal; Mohamed Sayed Zaazouee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Spontaneous intracerebral hemorrhage (sICH) is a serious form of stroke associated with high mortality and poor functional outcomes. Hematoma expansion critically affects prognosis, necessitating early intervention. Tranexamic acid (TXA), an antifibrinolytic, has an uncertain role in sICH. This meta-analysis synthesizes evidence from randomized controlled trials (RCTs) to evaluate the efficacy and safety of TXA in sICH. Comprehensive searches of PubMed, Scopus, Web of Science, and Cochrane Library identified RCTs comparing intravenous TXA to placebo in sICH, focusing on hematoma expansion. Data on functional outcomes, mortality, thromboembolic events, and quality of life were extracted. Cochrane RoB2 assessed the quality of studies. RevMan 5.4 was used for data analysis, employing fixed-effects models. Subgroup analyses were conducted based on time windows and patient subgroups. Eight RCTs (2974 patients) were included. TXA significantly reduced 24-h hematoma volume (MD = − 1.17 mL, 95% CI = − 1.97 to − 0.36), particularly when administered within 8 h (MD = − 1.71 mL, 95% CI = − 2.68 to − 0.74). However, odds of expansion, functional outcomes, 90-day mortality, thromboembolic events, and quality of life were similar between groups. Another subgroup analysis based on study populations revealed a significant effect of TXA on hematoma volume in studies involving sICH without a specific subgroup classification. However, no significant effect was observed in other subgroups, including sICH with spot sign, hypertensive ICH, and NOAC-associated ICH. TXA has been shown to reduce hematoma expansion in sICH, particularly when administered within 8 h of symptom onset, without a corresponding increase in thromboembolic events. However, this benefit has not translated into significant improvements in functional outcomes, mortality, or quality of life. As such, current evidence does not support the routine use of TXA in sICH, and further high-quality research is warranted.

Tracing contamination status and comprehensive risk assessment of potentially toxic elements in seawater impacted by shipping activities: The Red Sea, Egypt - Alaa M. Younis; Said Hanafy; Abdel-Aziz Y. El-Sayed; Mahmoud A. Ghandour; Eman M. Elkady; Naglaa F. Soliman (Marine Pollution Bulletin, 2025)

Femtosecond transient absorption spectroscopy investigation on Cu-MOF/g-C3N4 S-scheme heterojunction for photocatalytic CO2 reduction - Muhammad Sabir; Guogen Qiu; Songyu Yang; Muhammad Tahir; Jianjun Zhang; Mahmoud Sayed (Journal of Environmental Chemical Engineering, 2025)

Development and characterization of BSA-pullulan gel matrices incorporating orange peel flavonoids: Structural interactions and antimicrobial and antioxidant functionalities - Mahmoud Salah; Mabrouk Sobhy; Yajing Fang; Salwa M. El-Sayed; Ibrahim Khalifa; Ali Korin; Mohammed Mansour; Syed Asim shah Bacha; Sajid Maqsood; Yun Wang (Food Chemistry, 2025)

Berberine mitigates colitis-associated neuroinflammation and anxiety through modulation of the AMPK/NURR1 pathway - Esraa S. Habiba; Mona Hassan Fathelbab; Marwa M. AbdElaziz; Norhan S. El-Sayed; Marwa Mahmoud Mady; Gehad M. Khamis (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Balancing efficacy and hepatotoxicity: a comprehensive review of oral medications in psoriasis management - Alaa E. Elsisi; Sally El-Sayed Abu-Risha; Mahmoud Abdelrahman Alkabbani; Laila A. Ramadan; Samia Salem Sokar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Psoriasis is a chronic, immune-mediated inflammatory disorder that significantly impacts patients’ quality of life. Oral systemic therapies, including methotrexate, cyclosporine, acitretin, and apremilast, remain integral to psoriasis management, particularly for patients with moderate-to-severe disease who cannot afford biologic therapy. While these treatments are effective, their long-term use is often limited by adverse effects, particularly hepatotoxicity. Methotrexate and acitretin are associated with liver toxicity, requiring regular monitoring, whereas cyclosporine presents a lower but notable risk. Apremilast, a phosphodiesterase 4 inhibitor, offers a safer hepatic profile but has lower efficacy than traditional systemic agents. Emerging therapies, such as TYK2 inhibitors, RORγt inhibitors, and novel PDE4 inhibitors, aim to improve treatment efficacy while minimizing adverse effects. Advances in understanding hepatotoxicity mechanisms have led to identifying predictive biomarkers and hepatoprotective strategies, including antioxidants and non-invasive imaging techniques. Personalized medicine approaches, including pharmacogenomics, are revolutionizing treatment selection by optimizing efficacy while minimizing toxicity risks. This comprehensive review examines oral psoriasis treatments’ efficacy and hepatotoxicity profiles, discusses novel therapeutic developments, and explores strategies for mitigating liver-related adverse effects. A balanced approach that integrates clinical monitoring, lifestyle modifications, and emerging precision medicine techniques is essential for optimizing long-term treatment outcomes. Future research should focus on refining predictive models for drug-induced liver injury and developing targeted therapies with improved efficacy and safety profiles. Graphical Abstract Created in BioRender. Elgindy, A. (2025) https://BioRender.com/vcab653

Innovative perspectives on glioblastoma: the emerging role of long non-coding RNAs - Ahmed S. Doghish; Abdelhamid Mahmoud; Mai A. Abd-Elmawla; Mohamed Bakr Zaki; Nora M. Aborehab; Abdulrahman Hatawsh; Abdullah F. Radwan; Ghadir A. Sayed; Rewan Moussa; Mustafa Ahmed Abdel-Reheim; Osama A. Mohammed; Hanan Elimam (Functional & Integrative Genomics, 2025)

Antioxidants, immunotoxicological, and histopathological impacts of polypropylene microplastics emitted from paper cups on Clarias gariepinus and the ameliorating role of Spirulina and recovery - Zainab Eid; Usama M. Mahmoud; Hanem S. Abdel-Tawab; Alaa El-Din H. Sayed (Fish Physiology and Biochemistry, 2025)
Fish are particularly vulnerable to microplastics (MPs), especially polypropylene microplastics (PP-MPs), which are widely used and environmentally persistent. Despite their prevalence, little is known about their impact on fish immune systems. Thus, this study’s goal was to look at the antioxidants, immunotoxicological, and histopathological impact of PP-MPs on African catfish Clarias gariepinus and the ameliorating role of Spirulina and recovery. A total of 108 fish, weighing 125 ± 3 g and 27 ± 2 cm, were acclimated and divided into six experimental groups (in triplicate): control, PP-MPs-treated groups (0.14 and 0.28 mg/L), PP-MPs + Spirulina (200 mg/L), and Spirulina alone. Fish were exposed to treatments for 15 days, followed by a 45-day recovery period. Antioxidant enzymes (SOD, CAT, GST, MAD), immune biomarkers, and histopathological changes in the spleen and head kidney were assessed. PP-MPs exposure led to a significant ( p < .05) decline in antioxidant enzymes and immune biomarkers compared to controls, with increased melanomacrophage centers and tissue damage. Spirulina supplementation significantly improved immune and antioxidant responses, although some parameters, like MAD and histopathological alterations, showed incomplete recovery even after 45 days. PP-MPs have immunotoxic and oxidative effects on Clarias gariepinus , with partial recovery possible through Spirulina supplementation. However, full restoration of immune tissue morphology requires longer recovery periods. The observed immune alterations were closely associated with histopathological damage in key immune organs.

Microbiota-based therapies in oral health and disorders - Akram N. Salah; Youssef A. Doghish; Shaimaa O. Abbass; Reda M. Mansour; Ghadir A. Sayed; Nourhan H. Elshami; Sherif S. Abdel Mageed; Osama A. Mohammed; Ahmed I. Abulsoud; Mohamed Bakr Zaki; Esraa M. Mosalam; Mahmoud A. Elrebehy; et al. (Folia Microbiologica, 2025)
The human oral microbiome is a complex, dynamic ecosystem critically involved in maintaining oral health and contributing to systemic well-being. Many bacteria and fungi are involved in oral cavities such as Penicillium , Rhodotorula , Saccharomycetales , Streptococcus , Veillonella , Neisseria , Actinomyces , and Schizophyllum. Disruption of microbial homeostasis, or dysbiosis, underpins a wide spectrum of oral diseases, including dental caries, periodontal disease, endodontic infections, and mucosal conditions. Recent advances in microbiome research have elucidated the mechanisms by which pathogenic microbial consortia, such as the red complex ( Porphyromonas gingivalis , Tannerella. forsythia , and Treponema denticola ), synergistically promote disease progression through virulence factors, metabolic interactions, and biofilm formation. Emerging microbiome-based therapies, comprising probiotics, postbiotics, predatory bacteria, and using bacteriophages, offer promising adjuncts or alternatives to traditional antimicrobial approaches by restoring microbial balance, reducing pathogenic load, and modulating host immune responses. For instance, probiotic strains like Streptococcus salivarius and Lactobacillus spp. have demonstrated efficacy in reducing plaque, gingival inflammation, and pathogenic bacteria, as well as having significant immunological modulation, while postbiotics provide similar benefits with enhanced safety and stability. Additionally, predatory bacteria such as Bdellovibrio bacteriovorus show potential for selective bacterial elimination and combating periodontal diseases that are driven by Gram-negative anaerobes. Bacteriophages offer another precision tool for targeting oral pathogens by lysing bacteria upon replication. Finally, oral microbiota transplantation aimed at treating periodontal disease by restoring a balanced microbial community in the oral cavity. These innovative strategies, combined with a nuanced understanding of biofilm dynamics and host–microbe interactions, pave the way for personalized and ecologically sustainable oral health interventions. Continued research is essential to translate these promising approaches into clinical practice, optimize delivery systems, and elucidate long-term safety and efficacy.

Eco-friendly solutions: a comprehensive review of natural coagulants for sustainable water treatment - Sayed Kotb Ali; Moaz M. Abdou; Mostafa M. Emara; Rabie Saad Farag; Mahmoud F. Mubarak (Environmental Geochemistry and Health, 2025)
Water pollution and scarcity are escalating global challenges that necessitate the development of sustainable water treatment technologies. Coagulation-flocculation, a crucial method for water purification, has traditionally relied on chemical coagulants such as alum and ferric chloride. However, these chemical treatments are associated with significant drawbacks, including the generation of toxic sludge, disruption of water pH, high operational costs, and adverse environmental impacts. In response to these issues, natural coagulants derived from plants, animals, and microorganisms have emerged as promising eco-friendly alternatives. This review explores the mechanisms, applications, and environmental advantages of natural coagulants in water treatment. Studies demonstrate their effectiveness in removing turbidity, heavy metals, pathogens, and other pollutants from both surface and synthetic wastewater. Compared to chemical coagulants, natural alternatives produce less sludge, are less toxic, and offer a more sustainable and environmentally friendly solution to water treatment. However, challenges persist, particularly in terms of scalability, standardization, and cost-effectiveness. The performance of natural coagulants can vary depending on geographical origin, and the lack of standardized extraction methods hinders their large-scale application. Future research should focus on optimizing extraction processes, addressing scalability issues, and exploring hybrid systems that combine the benefits of both natural and chemical coagulants. The continued development of natural coagulants holds great promise for creating more sustainable, cost-effective, and environmentally friendly water treatment solutions. Graphical Abstract

Enhanced photocatalytic performance of Ag-doped CuWO₄ thin films prepared by chemical spray pyrolysis - Mohammed M. Gomaa; Mahmoud S. Abdel-Wahed; Mostafa Boshta; Mohamed H. Sayed (Environmental Science and Pollution Research, 2025)

The Shadli metavolcanic belt in the south Eastern Desert of Egypt: A late Tonian-Cryogenian hotspot track in the northern Arabian-Nubian Shield - Robert J. Stern; Mohamed Zaki Khedr; Martin Whitehouse; Madhusoodan Satish Kumar; Yuruo Shi; Mahmoud A. Sayed (Journal of African Earth Sciences, 2025)

Decoding the Gut Microbiota in Multiple Sclerosis Using Nanopore Long-Read Sequencing: Insights into Disease Severity and Subtypes - Ameera Saeed Alshinnawy; Elham A. Badiea; Mahmoud Saad Swelam; Ahmed A. Sayed; Mohamed R. Mohamed (Molecular Neurobiology, 2025)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS), characterized by neuroinflammation and neurodegeneration. Emerging evidence links gut microbiota dysbiosis to immune dysregulation and MS progression. While extensive research has been conducted in Western populations, region-specific studies are needed to assess the influence of local genetic and environmental factors. This study investigates gut microbiota alterations in Egyptian MS patients using Oxford Nanopore sequencing to identify microbial signatures associated with disease progression. Fecal samples from 33 newly diagnosed MS patients (20 with relapsing–remitting MS [RRM] and 13 with Progressive MS [PMS]) and 10 healthy controls were analyzed using long-read Oxford Nanopore sequencing of the full 16S rRNA gene. MS patients exhibited increased microbial richness but reduced evenness, with distinct gut microbiome profiles. Progressive MS was characterized by an abundance of pro-inflammatory bacteria (e.g., Enterococcus faecium and Romboutsia timonensis ) and a depletion of short-chain fatty acid (SCFA)–producing species ( Ruminococcus bromii and Faecalibacterium duncaniae ), potentially contributing to heightened neuroinflammation and disease progression. Relapsing MS exhibited microbial shifts indicative of immune dysregulation, including increased Clostridium saudiense and decreased levels of the gut-protective Faecalibacterium butyricigenerans . Functional analysis linked these microbial alterations to oxidative stress, neurotransmitter imbalance, and suppressed lipid and carbohydrate metabolism. These findings underscore the role of gut microbiota dysbiosis in MS pathogenesis and, by focusing on an underexplored Egyptian cohort, highlight region-specific microbial shifts that may inform targeted therapeutic strategies for both Progressive and Relapsing forms of MS.

Therapeutic potential of purpurin, a natural anthraquinone dye, in neuroprotection and neurological disorders - Aya M. Mustafa; Ghadir A. Sayed; Shymaa Hatem; Roxane Abdel-Gawad Moussa; Dina M. Hal; Mahmoud A. Mansour; Mohamed S. Abd El Hafeez (Inflammopharmacology, 2025)
Purpurin (1,2,4-trihydroxy-9,10-anthraquinone) is a naturally occurring anthraquinone pigment derived primarily from Rubia species. Beyond its traditional use as a natural dye, purpurin has recently gained attention for its multifaceted pharmacological activities, particularly in neuroprotection. This review outlines the biosynthetic pathways leading to anthraquinone formation via the shikimate, mevalonate, and methylerythritol phosphate routes, culminating in the generation of purpurin. Structure–activity relationship analyses highlight the critical role of hydroxyl substitutions in modulating antioxidant, anticancer, antibacterial, and neuroprotective properties through radical stabilization, DNA intercalation, and metal chelation. Evidence from preclinical studies indicates that purpurin exerts beneficial effects in Alzheimer’s disease, depression, ischemic stroke, and age-related cognitive decline, primarily through anti-tau aggregation, cholinesterase inhibition, serotonergic modulation, antioxidant activity, and anti-inflammatory mechanisms. While purpurin exhibits low acute toxicity and promising pharmacodynamics, its therapeutic translation remains limited by poor solubility, rapid metabolism, and low brain bioavailability. Nanotechnology-based formulations and molecular modifications are being explored to overcome these challenges. Collectively, purpurin represents a versatile bioactive scaffold with considerable potential for the development of multifunctional neuroprotective agents.

Supplementation of multi-strain probiotics in water enhances growth, metabolic responses, immune function, growth and immunity genes, and disease resistance in Nile tilapia (Oreochromis niloticus) - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Ahmed Saud Alsaqufi; Abdallah Tageldein Mansour; Nagarajan Ganesan; Mahmoud Mabrok; Zulhisyam Abdul Kari; Moaheda E.H. Eissa; Layla A. Almutairi; El-Sayed Hemdan Eissa (Aquaculture International, 2025)

Phytochemical insights and hepatoprotection evaluation of Heliotropium arbainense: Analyzing gene expression and therapeutic potential - Alsayed E. Mekky; Albayoumi A. Fouda; Osama Mohammad Mohammad Abdelhay; Kamal Rady Mohammed; Mohamed Arafat Mohamed Mansour; Mohamed A.M. El-Tabakh; Abeer Mahmoud Mohammad; Amani Alhejely; Taiseer Ahmed Shawky; Eslam S. Abdelmouty; Mohamed Khedr; Mahmoud Radwan; et al. (South African Journal of Botany, 2025)

Eco-friendly composite membranes of recycled PVC and Co-MOFs for efficient Ca2+ scale removal and anti-fouling in water treatment - Mennat Allah M. Ali; Mona El-Sayed; Omnia A.A. El-Shamy; Ghada E. Khedr; Magdy W. Sabaa; Riham R. Mohamed; Mahmoud F. Mubarak (Process Safety and Environmental Protection, 2025)

Butylated hydroxytoluene (BHT) improved semen quality and sperm DNA of frozen-thawed Arabian stallions preserved in modified INRA-82 extender - Amal M. Aboelmaaty; Islam El-Sayed El-Seadawy; Mohamed Saeed Kotp; Alaa A. Mohamed; Hazem Ahmed El-Debaky; Diya A. El-Badry; Abeer M. Anwer; Tsvetan Tsvetkov; Teodora Daneva; Mahmoud A. Elgabry (Journal of Equine Veterinary Science, 2025)

Microalgae as a source of carotenoids in foods, obstacles and solutions - Heba Sayed Mostafa; Marwa Mahmoud Hashem (Phytochemistry Reviews, 2025)
Recently, microalgae have attracted attention as a natural source of healthier bioactive molecules, especially carotenoids, because human bodies lack the ability to synthesize them, and their intake is necessary for human nutrition. Microalgae can produce various classes of these natural products, distinguished by their health benefits. In food sectors, microalgae are available as whole cells or as a source for extracting a specific carotenoid. This review summarizes recent knowledge of the biosynthesis pathway and the factors affecting carotenoid content, as well as strategies for increasing microalgae synthesis of various carotenoids. New uses of carotenoid-rich microalgae in food are highlighted, along with the main challenges and suggested solutions for using microalgal-carotenoids in the foodstuff. Carotenoids, particularly β-carotene and astaxanthin, face significant challenges in terms of bioavailability and stability when included in foods. Although many solutions were proposed, more research is required to determine the stability of other carotenoids under various food processing techniques. Furthermore, future studies should focus on improving bioavailability and accessibility after digestion in order to benefit from all added carotenoids. Modern technology and a fast-paced lifestyle necessitate the inclusion and acceptance of microalgal carotenoids, particularly for the most vulnerable populations, children, and pregnant women.

Phage therapy and its role in cancer treatment and control - Heba Ibrahim Abd El-Moaty; Ahmed S. Doghish; Hebatallah Ahmed Mohamed Moustafa; Wagiha S. Elkalla; Ghadir A. Sayed; Nourhan H. Elshami; Sherif S. Abdel Mageed; Osama A. Mohammed; Mahmoud A. Elrebehy; Kareem AlFarsi; Amr M. Abdelfatah; Aly M. Waseem; et al. (Folia Microbiologica, 2025)

Effect of dietary betaine on growth, physiological response, and immune-related genes in Chinese mitten crab (Eriocheir sinensis) - Nouran Mahmoud Sayed; Hesham Eed Desouky; Kenneth Prudence Abasubong; Hossam-eldin Seddik; Ziping Zhang (Aquaculture International, 2025)

Dietary spirulina platensis a promising growth promotor and immune stimulant in broiler chickens - Enas Mahmoud; Gehad Elsayed; Azza Hassan; Ahmed Ateya; Shimaa Abd El-Salam El-Sayed (Natural Product Research, 2025)

Oral Bee Venom as a Novel Therapeutic Approach for Diabetic Nephropathy in Rats: Role of PI3K, AMPK, and VEGF Signaling - Amany N. Ahmed; Dina H. Merzeban; Doaa E. Eldosoki Mohammed; Rania H. Mahmoud; Amr A.A. Metwally; Sayed M. Metwally Mizar (Toxicon, 2025)

Facile one-pot green chemistry approach with whiteness assessment for unveiling micellar-mediated fluorescence amplification of midodrine: A comprehensive study of analytical significance - Pakinaz Y. Khashaba; Mahmoud Abdelgaleel; Dalia M. Nagi; Mohamed Oraby; Sayed M. Derayea (Sustainable Chemistry and Pharmacy, 2025)

Environmental bovine subclinical mastitis gram-negative pathogens: Prevalence, antimicrobial resistance with special reference to extended-spectrum β-lactamases and carbapenemase production - Reda Abdel-Hameed; Hanan H. Abd-Elhafeez; Sara Salah Abdel-Hakeem; Mahmoud AlElaimi; Nagah M. Abourashed; Ashraf M. Ashmawy; Eshraqa Ali; Bader Huwaimel; Freah Alshammary; Alaa Sayed Abou-Elhamd; Mona Ahmed El-Zamkan (Research in Veterinary Science, 2025)

MicroRNAs in HIV infection: dual regulators of viral replication and host immunity - Reda M. Mansour; Gharieb S. El-Sayyad; Nehal I. Rizk; Sherif S. Abdel Mageed; Mohamed Salah Basiouny; Salma A. El-Sayed; Salma Zaki Fayez; Moustafa Mahmoud Abdelaziz; Khaled Abuelhaded; Haidy Adel Fahmy; Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Rutin-Loaded Nanocapsules Mitigate Vancomycin-Induced Hepatotoxicity: Development, Characterization, Optimization, and In Vivo Evaluation - Mohamed Ibrahim; Mohamed Fouad Mansour; Mahran Mohamed Abd El-Emam; Tarek khamis; Maha S. Kilany; Amira Ebrahim Alsemeh; Asmaa Monir Eltaweel; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed (Journal of Pharmaceutical Innovation, 2025)
Background Vancomycin (VCM)-induced hepatotoxicity is a significant clinical concern due to its association with oxidative stress, apoptosis, and inflammatory responses. This study investigated the formulation and potential preclinical application of rutin-loaded nanocapsules (RUT-NC) as a hepatoprotective agent against VCM-induced liver injury. Methods Hepatotoxicity was induced in rats through VCM administration, followed by oral treatment with RUT-NC. Liver function, oxidative stress markers, apoptotic proteins, lipid metabolism regulators, and inflammatory cytokines were subsequently evaluated. Results RUT-NC treatment significantly improved liver function parameters, attenuated oxidative stress, and modulated apoptotic pathways by downregulating the expression of p38 , p53 , caspase-8 , miR-122 , miR-7 , and beclin-1. Furthermore, RUT-NC restored lipid metabolism homeostasis by regulating the expression of PPAR-α, FASN, and SREBP-1. Notably, it exerted potent anti-inflammatory effects by suppressing NF-κB , TNF-α , IL-1β , IL-6 , IL-17 , and Gasdermin-D , thereby mitigating chronic liver inflammation. The pathological effects of VCM administration on hepatocytes were effectively counteracted by RUT-NC. Conclusion RUT-NC demonstrates promising hepatoprotective properties by enhancing antioxidant defenses, inhibiting apoptosis, regulating lipid metabolism, and reducing inflammation. These findings highlight its potential as a therapeutic intervention for drug-induced liver injury (DILI) and warrant further investigation for clinical application.

Nutritional and physiological effects of high-fat diets in finfish: effects on growth, immunity, lipid metabolism, and intestinal health: a review - Hesham Eed Desouky; Nouran Mahmoud Sayed; Kenneth Prudence Abasubong; Ziping Zhang (Journal of Comparative Physiology B, 2025)

Overcoming challenges in the analysis of the ubiquitous emerging contaminant trifluoroacetic acid employing trap column liquid chromatography tandem mass spectrometry - Ramadan Sayed; Ahmed A. Omran; Rabie S. Farag; Hend A. Mahmoud; Mostafa Soliman (Journal of Hazardous Materials, 2025)

Synthesis and antimicrobial evaluation of a new hybrid bis-cyanoacrylamide-based-piperazine containing sulphamethoxazole moiety against rheumatoid arthritis-associated pathogens - Mona M. Soliman; Ahmed H. M. Elwahy; Ahmed M. Sayed; Mahmoud Ibrahim; Mohamed A. Dawoud; Shahd Hisham Mohamed Ali; Menna Tallah S. Nady; Nada A. Hassan; Wessam Saad; Ismail A. Abdelhamid (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Piperazine-based compounds have garnered significant attention due to their notable biological and pharmacological activities, making them essential in fine chemical and pharmaceutical applications. In this study, we managed to synthesize a novel hybrid bis-cyanoacrylamide bearing the piperazine core via phenoxymethyl linker and incorporating sulphamethoxazole moiety. The novel compound was fully characterized using different spectral data including 1H-NMR, 13 C-NMR, and FTIR spectroscopy. Piperazine-based compounds were screened for in silico studies to understand the antimicrobial activity against infections that may contribute to rheumatoid arthritis symptoms. The tested piperazine compound was also evaluated for its antimicrobial activity against Aspergillus niger , Candida albicans , Enterococcus faecalis ATCC 29212, Staphylococcus aureus ATCC 29213, Pseudomonas aeuroginosa ATCC 27853, Escherichia coli ATCC 25922, and Klebsiella pneumoniae ATCC 700603. S. aureus showed the highest inhibition, with a zone diameter of 16.0 ± 1.0 mm at a concentration of 0.8 mg/ml. The minimal inhibitory concentration (MIC) for all bacterial species ranged from 5 to 40 mg/ml. In contrast, fungal species were the most resistant to the tested compound. Molecular docking studies were conducted to elucidate the interaction mechanisms, binding energies, and hydrogen bonding interactions within protein–ligand complexes. Molecular docking studies were performed against five bacterial proteins and two fungal proteins, including DNA gyrase subunit B (UniProt ID: Q839Z1), protein RecA of (UniProt ID: P0A7G6), cyclic AMP-AMP-AMP synthase (UniProt ID: P0DTF7), UDP-N-acetylglucosamine 1-carboxyvinyl transferase (UniProt ID: A0A1S5RKE3), and clumping factor A (UniProt ID: Q53653). The tested compound achieved the highest binding score of ∆G = − 10.9 kcal/mol at the cyclic AMP synthase active site (UniProt ID: P0DTF7), forming 26 interactions. The results demonstrated that the synthesized piperazine compound exhibits promising antibacterial and antifungal activities, highlighting its potential as a candidate for antimicrobial development.

Resveratrol mitigates heat stress-induced testicular injury in rats: enhancing male fertility via antioxidant, antiapoptotic, pro-proliferative, and anti-inflammatory mechanisms - Mona Hafez Hafez; Sara El-Sayed El-kazaz; Mahmoud S. El-Neweshy; Mustafa Shukry; Heba I. Ghamry; Hossam G. Tohamy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Remote sensing, petrogenesis and tectono-magmatic evolution of the Wadi Queh-Wadi Abu Shigeili area: a window into the transitional history of the central Egyptian-Nubian Shield from pre-plate collision to post-collision magmatism - Osama K. Dessouky; El-Sayed H. El-Sawey; Yasser S. Badr; Sobhi Nasir; Gehad M. Saleh; Ahmed M. Dardier; Kamal A. Ali; Abdel-Rahman Fowler; Saleh E. Ammar; Ahmed M. Ismail; Mahmoud M. Hassan (International Journal of Earth Sciences, 2025)

Targeting TLR4/NF-κB signaling, oxidative stress, and apoptosis by farnesol mitigates cadmium-induced testicular toxicity in rats - Emad H.M. Hassanein; Mohammed F. Alotaibi; Reem S. Alruhaimi; Mostafa Sabry; Ghadir A. Sayed; Ahmed M. Atwa; Ayman M. Mahmoud (Tissue and Cell, 2025)

Labour diagnostics using the intrauterine pressure through sound waves emitted by a smartphone - Benjamin Alderson; A. Osman; Mahmoud Ahmed El-Sayed; Khamis Essa (Medical & Biological Engineering & Computing, 2025)
Labour commencement diagnosis is still challenging in obstetrics. The majority of scientific techniques that were used to determine labour are costly and require a professional healthcare personnel to be carried out. Hence, in this work, an experiment was conducted using a 3D-printed 50% scale model of the abdomen of an average 40-week pregnant woman. The aim was to test whether the internal pressure can be evaluated from the reflection of the sound waves emitted by a smartphone. Frequencies of 4 kHz and 20 kHz were triggered at multiple distances (0.17, 0.34, 0.51 m) after inflating the 3D-printed model with water. The reflection coefficients and internal pressure were determined to have a positive linear correlation, suggesting that the hypothesis is practical. However, as the distances decreased, the reflection coefficient plateaued, indicating that the material had attained its maximum reflection coefficient at that frequency. Due to its reduced error and non-audible properties as compared to 4Hz, 20 kHz was suggested to be an optimum frequency for measuring pressure, allowing it for pain-free application for an extended amount of time. Graphical Abstract

BDCN_UNet: Advanced shoreline extraction techniques integrating deep learning - Amira S. Mahmoud; Sayed A. Mohamed; Ashraf K. Helmy; Ayman H. Nasr (Earth Science Informatics, 2025)
The delineation of shorelines, marking the dynamic boundary between land and sea, is crucial for coastal management and ecological conservation. This research investigates various methods for automatic shoreline extraction from satellite images, utilizing cost-effective and regularly available remote sensing data. A deep learning framework is used for the comparison that combines semantic segmentation (UNEt) and edge detection (Bi-Directional Cascade Network, or BDCN) to make the results more accurate. The study focuses on the northern coast of Egypt, a region with diverse landscapes and significant human interventions. We’ve made progress in our methods by using advanced image processing, the CoastSat Toolkit, the BDCN_UNet framework, time series analysis, and deep learning networks to look at and keep an eye on Egypt’s North Coast’s future plans in more detail. This study captures the intricate interplay between natural and human factors in coastal environments, offering valuable insights for sustainable coastal development. The performance analysis of four models (UNet, Pyramid Scene Parsing Network, DeepLabV3, and BDCN_UNet) applied to three satellite datasets (Sentinel-2, PlanetScope, and Pleiades) showed that PlanetScope and Pleiades consistently yield higher accuracy (0.90–0.99), while Sentinel-2 proved more challenging, particularly for Pyramid Scene Parsing Network and DeepLabV3. UNet and BDCN_UNet exhibited robust performance across all datasets, especially with Pleiades delivering the best results overall.

Investigating the effects of granite, marble, granodiorite, and ceramic waste powders on the physical, mechanical, and radiation shielding performance of sustainable concrete - Alaa A. Mahmoud; Alaa A. El-Sayed; Ayman M. Aboraya; Islam N. Fathy; Mohamed A. Abouelnour; Bassam A. Tayeh; Islam M. Nabil (Annals of Nuclear Energy, 2025)

Aeromonas veronii infection in cultured Oreochromis niloticus: prevalence, molecular and histopathological characterization correlated to water physicochemical characteristics, with the protective autochthonous probiotic - Amr Fadel; Mahmoud A. Mahmoud; Mohamed Abdelsalam; El-Sayed Hemdan Eissa; Ahmed H. Sherif (Aquaculture International, 2025)
This study characterized the bacterial pathogen associated with summer mortality in cultured Nile tilapia ( Oreochromis niloticus ) between June and August 2024 across two different farms. As well as, the autochthonous probiotic was isolated as a preventive strategy. Phenotypic characteristics identified Aeromonas veronii and confirmed by molecular sequencing of the gyrB gene. Total prevalence was higher in farm 1 (65.19%) than in farm 2 (51.11%), with respective mortality rates of 38.84% and 25.25%. Prevalence rates peaked in August, which was correlated significantly ( P ≤ 0.05) with elevated water temperature, pH, ammonia, and salinity. Clinical signs included erratic swimming, skin hemorrhages, and corneal opacity, with necropsy including ascitic fluids, friable liver, and splenomegaly. Challenge assay confirmed LD50 of 2.7 × 10 7 CFU/mL A. veronii and 66.67% cumulative mortality. Histopathological alterations showed intermuscular edema, glomerular atrophy of the kidneys, vacuolar degeneration of the liver, spleen necrosis, and hemosiderosis of intestinal tissues. A. veronii showed resistance to ampicillin, tigecycline, fosfomycin, and sulfamethoxazole-trimethoprim. To control Aeromonas infection, 18 autochthonous probiotic isolates were obtained from the healthy O. niloticus gut and identified as Bacillus paralicheniformis through phenotypic analysis and 16S rRNA gene sequencing. These probiotic isolates demonstrated strong antagonistic activity against the pathogenic A. veronii , ecto-enzymatic producing activities, and high bile salt tolerance. After comprehensive screening, seven Bacillus strains met safety criteria, exhibiting high sensitivity to antimicrobials, non-hemolytic activity, and non-pathogenic in the challenge test. This study confirms A. veronii as the causative agent of tilapia summer mortality and presents promising autochthonous probiotics for preventive strategies in aquaculture.

Zinc-based metal–organic frameworks for sustainable water desalination and anti-scaling solutions - Mennat Allah M. Ali; Mona El-Sayed; Omnia A. A. El-Shamy; Ghada E. Khedr; Magdy W. Sabaa; Riham R. Mohamed; Mahmoud F. Mubarak (Environmental Science and Pollution Research, 2025)

Optimizing dehydration and viscosity reduction in Egyptian heavy crude oil emulsions using eco-friendly demulsifiers - Ahmed Z. Ibrahim; El Sayed H. El tamany; Mostafa A.A. Mahmoud; Mokhtar Al-Abyadh; H.A. El Nagy (Fuel, 2025)

Structural and Energetic Insights into the Binding of L- and D-Arginine Analogs with Neuropilin-1 (NRP1): Molecular Docking, Molecular Dynamics and DFT Calculations - Mahmoud A. A. Ibrahim; Dina E. M. Mohamed; Khlood A. A. Abdeljawaad; Alaa H. M. Abdelrahman; Shaban R. M. Sayed; Mohamed A. El-Tayeb; Peter A. Sidhom; Paul W. Paré (Cell Biochemistry and Biophysics, 2025)

Eco-friendly management of Fusarium wilt in tomato using Salvia officinalis methanolic extract: in vitro, in vivo, and molecular docking approaches - Mahmoud A. Gaber; Sarah El-Messeiry; Rania El-Tanbouly; Amany Assem Elkashef; Said I. Behiry; Sayed S. Aboshosha; Helmy A. Aamer (Journal of Plant Pathology, 2025)
Fusarium wilt, caused by Fusarium oxysporum f. sp. lycopersici , threatens global tomato production, with losses reaching 80%. Although chemical fungicides are effective, their prolonged use risks resistant strains, reduces soil biodiversity, and causes environmental damage, highlighting the urgent need for ecofriendly alternatives. This study investigated the viability of Salvia officinalis (sage) methanolic extract as a biocontrol agent against Fusarium wilt (FW), employing a comprehensive approach that incorporates in vitro, in vivo, and molecular docking techniques. Four distinct isolates of F. oxysporum were identified through molecular techniques, and their virulence was assessed by examining the presence of tomatinase genes. The antifungal properties of S. officinalis extract were found to be compelling, with a total phenolic content of 64.15 mg GAE/g and a remarkable antioxidant activity of 97.04%. In laboratory tests, S. officinalis exhibited potent antifungal activity, inhibiting mycelial growth by between 52.00% and 88.67% at a concentration of 20 mg/ml. Additionally, in vivo experiments demonstrated a significant reduction in disease severity in treated tomato plants. Molecular docking analyses revealed strong binding affinities between key phytochemicals in the extract and target receptors such as tomatinase, highlighting the potential of the extract as a sustainable and effective alternative to chemical fungicides for managing FW in tomato crops.

Vitamin D3 mitigates aspirin-induced gastric injury by modulating gastrokines, E-cadherin, and inhibiting NLRP3 and NF-κB/MMP-9 signaling pathway - Sherein F. El-sayed; Samar Mortada Mahmoud; Walaa Samy; Reham M. Wahid; Aliaa Talaat; Sara G. Seada (Tissue and Cell, 2025)

Decorin alleviates non-alcoholic fatty liver disease in rats with polycystic ovary syndrome - Hany A. Elkattawy; Amira Ebrahim Alsemeh; Lashin Saad Ali; Mona Mostafa Ahmed; Asmaa Monir Eltaweel; Farha M. Shaikh; Ahmed Behiry; Ahmed El-Sayed Hassan; Deema Kamal Sabir; Dalia Mahmoud Abdelmonem Elsherbini; Sahar K. Ali; Madaniah Omar Zakari; et al. (Tissue and Cell, 2025)

Avocado fruit peel and flesh as antioxidant and anti-inflammatory agents: A comparative phytochemical and in vitro study - Dina Atef Waly; Aisha Hussein Abou Zeid; El-Sayeda Ahmed El-Kashoury; Sherifa Fahmy Moustafa; Ali Mahmoud El-Halawany; Reda Sayed Mohammed (South African Journal of Botany, 2025)

Insights into biochemical, genotoxic, and molecular impacts, and molecular docking analysis-based possible mechanism of action of some essential oils against Culex pipiens larvae - Salwa I. Sebak; El-Sayed H. Shaurub; Shaymaa H. Mahmoud; Sherehan A.R. Salem (Pesticide Biochemistry and Physiology, 2025)

Regeneration of dimethyl carbonate and purification of 5-hydroxymethylfurfural used in a biphasic dehydration process through activated carbon adsorption and evaporation - Mikael Sjölin; Mahmoud Sayed; Daniel Espinoza; Simon Tallvod; Basel Al-Rudainy (Journal of Environmental Chemical Engineering, 2025)

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Efficient photoreforming of organic solvents into CH4 over 2D donor-π-acceptor conjugated polymers with tunable symmetry - Guoen Tang; Xiangjing Xie; Guanhui Liu; Ting Song; Xiayi Hu; Bei Long; Guo-Jun Deng; Mahmoud Sayed (Chemical Engineering Journal, 2025)

The effect of adipose-derived mesenchymal stem cells against high fructose diet induced liver dysfunction and dysbiosis - Marwa Abdeltawab Mohammed; Nesma Hussein Abel Hay; Maha Tarek Mohammed; Hoda Sayed Mahmoud; Manar Yehia Ahmed; Ahmed Abdelmenem; Dina Sayed Abdelrahim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
High fructose diet (HFrD) has been approved to be involved in the pathogenesis of insulin resistance. Mesenchymal stem cells have a vital role in the treatment of various diseases including metabolic disturbances. We investigated the effect of Adipose-derived mesenchymal stem cells (ADMSCs) against HFrD-induced metabolic disorders and the molecular mechanisms for this effect. Rats were divided into 3 groups; control, HFrD, and combined HFrD with ADMSCs. We assessed liver functions, gut microbiota activity, oxidative stress, adiponectin, and IL10 levels. Also, we measured SREBP-1, IRS-1 expression using Western blot, and Malat1 expression using rt-PCR. ADMSCs antagonized metabolic abnormalities induced by HFrD in the form of improvement of liver functions and alleviation of oxidative stress. In addition, ADMSCs ameliorated gut microbiota activity besides the elevation of adiponectin and IL10 levels. ADMSCs attenuated insulin resistance through upregulation of IRS1 and downregulation of SREBP-1 and Malat1. ADMSCs can protect against HFrD-induced metabolic hazards.

Optimizing logic-tree branches for improved seismic hazard mapping in Egypt - Sayed S. R. Moustafa; Hanan Gaber; Mahmoud S. Elhadidy; Saleh Qaysi; Abdalla Abdelnabi (Journal of Seismology, 2025)

Pioneering study of Egyptian Neem and Jojoba extracts with molecular docking combat hospital multidrug resistant bacteria - Toka Khairy; Dina Hatem Amin; Hanaa Mohamed Salama; Iman Mohamed Amin Elkholy; Mostafa Elnakib; Hassan Mahmoud Gebreel; Hayam Abd Elnabi Sayed (Brazilian Journal of Microbiology, 2025)

Chemopreventive effect of Pistacia vera leaf extract against mammary carcinoma induced by dimethyl-benz(a)anthracene in vivo and in vitro: Potential role of antioxidant, antiinflammatory and immune mechanisms - Ali G. Alkhathami; Esmail M. El-Fakharany; Mohamed H. El-Sayed; Ahmed Atwa; Fatma Khairallah Ali; Nashwa Hamad; Hussam Askar; Mahmoud Ashry (Food and Chemical Toxicology, 2025)

Neuroprotective effect of red dragon fruit extract ameliorates oxidative stress and inflammation in D-galactose-induced aging rat model: biochemical, histological and immunohistochemical study - Manar Fouli Gaber Ibrahim; Fatma F. Ali; Sayed Fouad El-Sheikh Ali; Emad S. Shaker; Hemdan I. Mahmoud; Fatma ElZahraa Mohammed Abdellatif; Sahar A. Mokhemer (Journal of Molecular Histology, 2025)

Differential effects of liraglutide naltrexone/bupropion, and caloric restriction on metabolic parameters and beta-cell regeneration in type 2 diabetic rat model: role of beta arrestin 1 - Dina H. Merzeban; Amani M. El Amin Ali; Reem O. Hammad; Mohamed H. Elmahdi; Marwa A. Sofi; Rania H. Mahmoud; Sayed M. Metwally; Ahmed M. El Ebiary (Journal of Molecular Histology, 2025)

The evolving multidrug-resistant V. alginolyticus in sea bream commonly harbored collagenase, trh, and tlh virulence genes and sul1, blaTEM, aadA, tetA, blaOXA, and tetB or tetM resistance genes - Abdelazeem M. Algammal; Mahmoud Mabrok; Khyreyah J. Alfifi; Saad Alghamdi; Dalia M. Alammari; Madeha O. I. Ghobashy; Mohammad Y. Alshahrani; Azza S. El-Demerdash; El-Sayed Hemdan Eissa; Aya M. Elalamy; Reham M. El-Tarabili (Aquaculture International, 2025)

Correction to: 17β-Estradiol augments the neuroprotective effect of agomelatine in depressive- and anxiety-like behaviors in ovariectomized rats - Yasmine A. El-Khatib; Rabab H. Sayed; Nada A. Sallam; Hala F. Zaki; Mahmoud M. Khattab (Psychopharmacology, 2025)

The gut brain axis, effect of dietary changes and probiotics supplement on depression symptoms - Salma Hosny Abd-allah Mohamed; Ghada Mahmoud Khafagy; Inas El Sayed; Hala Ahmed Hussein (PharmaNutrition, 2024)

Bidentate bromhexine drug coordination modes with various transition metal ions: Synthesis, characterization, and in vitro antibacterial and anti-breast cancer activity tests - Fatma Nabil Sayed; Norhan Refaie Omar; Nessma Fathi Mahmoud; Gehad Genidy Mohamed (Journal of Trace Elements in Medicine and Biology, 2024)

Molecular typing of Protoparvovirus carnivoran 1 in Egyptian cats diagnosed with feline panleukopenia - Mahmoud S. Safwat; Samah El-Sayed M.; Mohamed E. Ali; Omar S. Saeed; Haitham M. Amer; Othman N.O. Mansour; Ayah M. Hassan; Manar M. Farouk (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Soil–plant Integrative Supplementation with Humic Acid and Antioxidants Improves Growth, Fruit Quality, and Antioxidant Capacity of Cd-stressed Solanum Melongena - Ali A. S. Sayed; Zahra Seoudi; Ashraf Sh. Osman; Wael M. Semida; Mostafa M. Rady; Amr Elkelish; Amr E. M. Mahmoud (Journal of Soil Science and Plant Nutrition, 2024)

Strengthening growth, digestion, body composition, haemato-biochemical indices, gene expression, and resistance to Fusarium oxysporum infection and histological structure in Oreochromis niloticus by using fructooligosaccharides and β-1,3 glucan mixture - Yasmin M. Abd El-Aziz; Fatima A. Jaber; Nada Mahmoud Nass; Ohaad F. Awlya; Wafaa F. Abusudah; Alaa H. Qadhi; Alya Redhwan; El-Sayed Hemdan Eissa; Hagar Sedeek Dighiesh (Aquaculture International, 2024)
Prebiotics are fibers that promote beneficial gut bacteria and play a pivotal role in enhancing host health. This study delves into the impact of various levels of prebiotics, specifically fructooligosaccharides and β-1,3 glucan (Fβ), on the growth performance, biochemical, hematological parameters, gene expression, histological variations in the internal organs, and disease resistance to Fusarium oxysporum in tilapia ( Oreochromis niloticus ). Two hundred forty Nile tilapia, initially weighing 34.0 ± 0.1 g, were distributed into four groups and given a commercial diet with varying Fβ treatments: control (0 g/kg) (C), T1 (0.5 g/kg), T2 (1.0 g/kg), and T3 (1.5 g/kg) for 70 days. The study revealed significant improvement of the biochemical, hematological, and digestive enzyme activities, as well as histological changes in hepatopancreatic, intestine, and spleen sections with the use of Fβ. Moreover, the expression of innate humoral genes significantly increased ( P F. oxysporum exhibited lower mortality rates in the three treatments supplemented with additive prebiotics ( P

Challenging the negative perceptions of key stakeholders towards aquaculture sector in Egypt: Evidence-based solutions - Mahmoud M. Abdel-Hady; Thanaa El-Noby; Ahmed M. Nasr-Allah; Seham A. Hashem; Zeinab M. Abdel-Khalek; Shaimaa M. Haggag; Abdel-Fattah M. El-Sayed (Marine Policy, 2024)

6-Paradol exhibits antimicrobial, anti-quorum sensing and anti-virulence capacities on gram-negative bacteria: In vitro and in vivo studies - Hassan M. Okairy; Abdulrahman E. Koshak; Mahmoud A. Elfaky; Hossam M. Abdallah; Gamal A. Mohamed; Sabrin R.M. Ibrahim; Abdulrahim A. Alzain; El-Sayed Khafagy; Azza A.H. Rajab; Wael A.H. Hegazy (South African Journal of Botany, 2024)

GIS-Based Flash Flood Hazard Evaluation in Helwan-Atfih Area, Egypt - Safinaz A. A. Mahmoud; Sayed Mosaad; I. Z. El-Shamy; Maysa M. N. Taha (Journal of the Indian Society of Remote Sensing, 2024)

Spectrofluorimetric Protocol for Estimation of Commonly Used Antispasmodic Drotaverine. Fluorescence Quenching Study - Sayed M. Derayea; Nihad A. Mahmoud; Deena A. M. Noureldeen; Tamer Z. Attia (Journal of Fluorescence, 2024)
A fast, simple, accurate, precise, and cheap fluorimetric protocol has been proposed for analysis of a phosphodiesterase-IV inhibitor, namely drotaverine hydrochloride. Fluorimetric protocol is based on estimating the decrease in the eosin Y fluorescence intensity by quantitative addition of drotaverine at pH 3.1 (acetate buffer). An ion pair complex is formed, which leads to quenching in the fluorescence intensity of the dye without need of prior extraction at 534 nm (λ ex . 339 nm). Different reaction perimeters which influence the production of complex (ion pair between drotaverine and eosin) were deeply investigated and optimized. The developed fluorimetric protocol is capable for quantitative estimation of drotaverine in linear range of 0.4 to 2.5 µg mL −1 . After method validation in respect to ICH guidelines, it was applied to determine drotaverine in its commercial preparation. By comparing with other reported method, the developed and validated fluorimetric protocol is capable for estimation of drotaverine in commercial preparation with good accuracy and excellent precision.

Farnesol attenuates cadmium-induced kidney injury by mitigating oxidative stress, inflammation and necroptosis and upregulating cytoglobin and PPARγ in rats - Reem S. Alruhaimi; Emad H.M. Hassanein; Ahmad F. Ahmeda; Ahmed M. Atwa; Sulaiman M. Alnasser; Ghadir A. Sayed; Meshal Alotaibi; Mohammed A. Alzoghaibi; Ayman M. Mahmoud (Tissue and Cell, 2024)

Towards the preparation of sustainable superplasticizers for geopolymeric pastes via radiation-induced grafting of sulfonic group-bearing monomers onto corn starch - Noha M. Deghiedy; Safaa M.A. El-Gamal; Mohamed Ramadan; Alaa Mohsen; Mahmoud M. Hazem; Mostafa A. Sayed; Fatma M. Helmy; Mona M. Wetwet; Ahmed E. Swilem (Carbohydrate Polymers, 2024)

Automatic Building Extraction from Multispectral LiDAR Using Novel 3D Spatial Indices and Deep Learning Point CNN - Asmaa A. Mandouh; Mahmoud El Nokrashy O. Ali; Mostafa H. A. Mohamed; Lamyaa Gamal E. L.-Deen Taha; Sayed A. Mohamed (Journal of the Indian Society of Remote Sensing, 2024)

Applications of bacteriophage in combination with nisin for controlling multidrug-resistant Bacillus cereus in broth and various food matrices - Marwa Nabil Sayed Abdelaziz; Aye Thida Maung; Mohamed El‐Telbany; Su Zar Chi Lwin; Tahir Noor Mohammadi; Mahmoud Zayda; Chen Wang; Catherine Hofilena Damaso; Yunzhi Lin; Yoshimitsu Masuda; Ken-ichi Honjoh; Takahisa Miyamoto (Food Research International, 2024)

Neurological and neurobehavioral effects of welders in Egypt exposed to manganese containing welding fumes - Gaafar Mohamed Abdel-Rasoul; Mahmoud El-Sayed Abu-Salem; Eman Abdel-Azeem Salem; Heba Khodary Allam; Amira Mohamed Abdel-Monaem; Faten Ezzelarab Younis (International Archives of Occupational and Environmental Health, 2024)

Single and combined application of bacteriophage and cinnamon oils against pathogenic Listeria monocytogenes in milk and smoked salmon - Aye Thida Maung; Marwa Nabil Sayed Abdelaziz; Tahir Noor Mohammadi; Su Zar Chi Lwin; Mohamed El-Telbany; Junxin Zhao; Chen Wang; Yunzhi Lin; Cunkuan Shen; Mahmoud Zayda; Yoshimitsu Masuda; Ken-ichi Honjoh; et al. (International Journal of Food Microbiology, 2024)

Enhanced upregulation of SIRT1 via pioglitazone and ligustrazine confers protection against ethanol-induced gastric ulcer in rats - Sara A. Mahmoud; Abeer Elkhoely; Elsayed K. El-Sayed; Amany A. E. Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Gastric ulcer is a disturbing disease that impacts many people worldwide. Pioglitazone (Piog), a thiazolidinedione, and ligustrazine (Ligu), a natural component of Ligusticum chuanxiong possess gastroprotective properties. However, the underlying mechanism is not well elucidated. The present study aimed to investigate the gastroprotective effects of Piog (15 mg/kg, p.o.), Ligu (15 mg/kg, p.o.), and their combination against ethanol-induced gastric ulcer in rats. Omeprazole (10 mg/kg) was used as a standard. Pre-treatment for 7 days with Piog, Ligu, and (Piog+Ligu) effectively alleviated ethanol-predisposed oxidative stress and inflammation through restoring HO-1, GSH, and SOD tissue levels and decreasing elevated MDA, TNF-α, ICAM, I-NOS, and IL-1β contents. Moreover, Piog, Ligu, and (Piog+Ligu) markedly inhibited the ethanol-induced increase of gastric NF-KB and BAX. In contrast, this pre-treatment regimen significantly accelerated protein expression of SIRT1, Nrf2, and Bcl-2, along with autophagic proteins, ATG5 and Beclin. Interestingly, macroscopic, histopathological examination and mucin content were in harmony with previous results, where pre-treatment with Piog, Ligu, and (Piog+Ligu) showed a declined mucosal injury as evidenced by the remarkable decrease of the ulcer area percentage by 62.3%, 38.7%, and 91.2%, respectively, compared to the ethanol-ulcerated group. In conclusion, Piog and Ligu exhibited remarkable gastroprotective properties. Our study was the first to show that Piog, Ligu, and (Piog+Ligu) ameliorated oxidative stress, inflammation, and apoptosis and accelerated the autophagic process via the upregulation of the upstream SIRT1 protein. It is worth mentioning that future studies are needed to pave the way for the clinical use of Piog and Ligu as gastro-protective agents.

Key aspects of polymeric nanofluids as a new enhanced oil recovery approach: A comprehensive review - Khalaf G. Salem; Mahmoud A. Tantawy; Ahmed A. Gawish; Adel M. Salem; Sayed Gomaa; A.N. El-hoshoudy (Fuel, 2024)

Possible beneficial effects of nano chitosan against doxycycline toxicity in Nile tilapia (Oreochromis niloticus) - Mahmoud S. Sabra; Mohamed Abd El-Aal; Shaimaa K.A. Idriss; Hamdy A.M. Soliman; Sally M. Salaah; Alaa El-Din H. Sayed (Aquaculture, 2024)

New models for estimating minimum miscibility pressure of pure and impure carbon dioxide using artificial intelligence techniques - Ahmed Ashraf Soliman; Sayed Gomaa; John S. Shahat; Fares Ashraf El Salamony; Attia Mahmoud Attia (Fuel, 2024)

Combined effect of pantoprazole and mesenchymal stem cells on experimentally induced gastric ulcer: implication of oxidative stress, inflammation and apoptosis pathways - Alaa H. Sayed; Nadia S. Mahmoud; Ola A. M. Mohawed; Hanaa H. Ahmed (Inflammopharmacology, 2024)
Gastric ulcer (GU) is one of the most common diseases of the upper gastrointestinal tract that affects millions of people worldwide. This study aimed to investigate the possible alleviating effect of a combined treatment of pantoprazole (PANTO) and adipose tissue-derived mesenchymal stem cells (ADSCs) in comparison with each treatment alone on the healing process of the experimentally induced GU in rats, and to uncover the involved pathways. Rats were divided into five groups: (1) Control, (2) GU, (3) PANTO, (4) ADSCs and (5) ADSCs + PANTO. Markers of oxidative stress, inflammation and apoptosis were assessed. The current data indicated that PANTO-, ADSCs- and ADSCs + PANTO-treated groups showed significant drop ( p < 0.05 ) in serum advanced oxidation protein products (AOPPs) and advanced glycation end products (AGEPs) along with significant elevation ( p < 0.05 ) in serum TAC versus the untreated GU group. Moreover, the treated groups (PANTO, ADSCs and ADSCs + PANTO) displayed significant down-regulation ( p < 0.05 ) in gastric nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), tumor necrosis factor alpha (TNF-α), cyclooxygenase-2 (COX-2), intercellular adhesion molecule-1 (ICAM-1), matrix metallopeptidase 9 (MMP - 9) and caspase-3 along with significant up-regulation ( p < 0.05 ) in vascular endothelial growth factor (VEGF) and peroxisome proliferator-activated receptor gamma (PPARγ) genes expression compared to the untreated GU group. Immunohistochemical examination of gastric tissue for transforming growth factor β1 (TGF-β1), epidermal growth factor (EGF) and proliferating cell nuclear antigen (PCNA) showed moderate to mild and weak immune reactions, respectively in the PANTO-, ADSCs- and ADSCs + PANTO-treated rat. Histopathological investigation of gastric tissue revealed moderate to slight histopathological alterations and almost normal histological features of the epithelial cells, gastric mucosal layer, muscularis mucosa and submucosa in PANTO-, ADSCs- and ADSCs + PANTO-treated rats, respectively. Conclusively, the co-treatment with ADSCs and PANTO evidenced sententious physiological protection against GU by suppressing oxidative stress, inhibiting inflammation and reducing apoptosis with consequent acceleration of gastric tissue healing process.

Impact of novel chloride-binding on strength, chloride penetration and resistance to corrosion of concrete exposed to chloride-bearing environment - Esraa S. Ibrahim; Mahmoud Gharieb; Mohamed R. Sakr; Hamdy A. El-Sayed; Mohamed O. R. El Hariri (Innovative Infrastructure Solutions, 2024)

Physicochemical, texture, microstructure, and antioxidant characteristics of karish cheese made from ultrasonic-treated skimmed buffalo milk - Aliaa Ali Darwish; Mahmoud Ibrahim El-Sayed; Wafaa Mahmoud Salama (International Dairy Journal, 2024)

Flooded architecture as an adaptation tool for climate change impact—a case study of possible interpretation in Egypt - Rasha Sayed Mahmoud; Shereen Abou Dagher; Passant Youssef (Innovative Infrastructure Solutions, 2024)
In light of the current global environmental issues, such as floods, underground water problems, and soil salinity, there is a growing need for sustainable architectural and housing solutions that can effectively address the impact of these challenges on food and security (Nation 2002). In Egypt, frequent incidents of flooding and sinking roads and cities are observed, particularly after rainfall or in projects that involve underground water drainage (UN-Habitat 2022). This paper explores the concept of flooded architecture, which involves designing buildings and spaces that are intentionally flooded with water. Through a review of relevant literature and case studies, the paper investigates the potential benefits and drawbacks of this approach nationally inside Egypt, structure, and construction used materials, including its impact on energy efficiency, sustainability, and resilience to natural disasters. The findings suggest that flooded architecture has the potential to offer innovative solutions for a range of environmental and social challenges but also raises important questions around safety, maintenance, and cultural acceptance in Egypt.

Bi-stage feature selection for crop mapping using grey wolf metaheuristic optimization - Marwa S. Moustafa; Amira S. Mahmoud; Eslam Farg; Mohsen Nabil; Sayed M. Arafat (Advances in Space Research, 2024)

Immunomodulatory and antioxidant properties of Sarcophaga argyrostoma larval hemolymph: utilizing the Biomphalaria alexandrina snail as a model - Alya Mashaal; Asmaa A. Abo Elqasem; Lina A. Abou El-Khashab; Hend M. El-Menyawy; Basma M. Abou El-Nour; Eman M. Abdullah; Asmaa M. Abdalkareem; Rawda A. Al-gebaly; Asmaa M. El-sayed; Ghada R. Mabrok; Rawda R. Mahmoud; Dina A. Ali; et al. (Biologia, 2024)
In recent years, there has been a growing interest in exploring novel natural sources for antioxidant and anti-inflammatory agents, driven by the need for alternative therapeutic strategies with fewer side effects. This study investigates the potential of the Biomphalaria alexandrina snail as a valuable model organism to evaluate the antioxidant and anti-inflammatory properties of Sarcophaga argyrostoma larval hemolymph. The choice of B. alexandrina snails as a model is based on its ecological relevance and physiological similarities to other organisms, supporting well-established use in ecological and physiological research, as well as it provides a valuable platform for such investigations. Ultimately, this study may open avenues for the development of innovative and sustainable therapeutic interventions rooted in the rich biodiversity of the natural world. The experimental design involves the extraction of hemolymph from S. argyrostoma larvae, followed by a comprehensive analysis of its antioxidant capacity and anti-inflammatory effects using adult snails. Various biochemical assays, including total antioxidant capacity, immunomodulatory markers and histological investigation, will be employed to assess the bioactive potential of the hemolymph. The outcomes of this research can be attributed to the identification of the anti-oxidant and anti-inflammatory effects of hemolymph. This effect was observed through the reduction of oxidative stress and proinflammatory mediators, impacting the biological activities of the snails. The study is the first to shed light on the potential benefits of S. argyrostoma larval hemolymph using an animal model, showcasing its ability to mitigate oxidative and inflammatory responses within the biological context of the snails.

Neuroprotective potential of Erigeron bonariensis ethanolic extract against ovariectomized/D-galactose-induced memory impairments in female rats in relation to its metabolite fingerprint as revealed using UPLC/MS - Weam W. Ibrahim; Rabab H. Sayed; Mohamed F. Abdelhameed; Enayat A. Omara; Mahmoud I. Nassar; Noha F. Abdelkader; Mohamed A. Farag; Abdelsamed I. Elshamy; Sherif M. Afifi (Inflammopharmacology, 2024)
Erigeron bonariensis is widely distributed throughout the world's tropics and subtropics. In folk medicine, E. bonariensis has historically been used to treat head and brain diseases. Alzheimer’s disease (AD) is the most widespread form of dementia initiated via disturbances in brain function. Herein, the neuroprotective effect of the chemically characterized E. bonariensis ethanolic extract is reported for the first time in an AD animal model. Chemical profiling was conducted using UPLC–ESI-MS analysis. Female rats underwent ovariectomy (OVX) followed by 42 days of D-galactose (D-Gal) administration (150 mg/kg/day, i.p) to induce AD. The OVX/D-Gal-subjected rats received either donepezil (5 mg/kg/day) or E. bonariensis at 50, 100, and 200 mg/kg/day, given 1 h prior to D-Gal. UPLC–ESI-MS analysis identified 42 chemicals, including flavonoids, phenolic acids, terpenes, and nitrogenous constituents. Several metabolites, such as isoschaftoside, casticin, velutin, pantothenic acid, xanthurenic acid, C18-sphingosine, linoleamide, and erucamide, were reported herein for the first time in Erigeron genus. Treatment with E. bonariensis extract mitigated the cognitive decline in the Morris Water Maze test and the histopathological alterations in cortical and hippocampal tissues of OVX/D-Gal-subjected rats. Moreover, E. bonariensis extract mitigated OVX/D-Gal-induced Aβ aggregation, Tau hyperphosphorylation, AChE activity, neuroinflammation (NF-κBp65, TNF-α, IL-1β), and apoptosis (Cytc, BAX). Additionally, E. bonariensis extract ameliorated AD by increasing α7-nAChRs expression, down-regulating GSK-3β and FOXO3a expression, and modulating Jak2/STAT3/NF-ĸB p65 and PI3K/AKT signaling cascades. These findings demonstrate the neuroprotective and memory-enhancing effects of E. bonariensis extract in the OVX/D-Gal rat model, highlighting its potential as a promising candidate for AD management. Graphical Abstract

Safety and efficacy of extended versus standard interval dosing of natalizumab in multiple sclerosis patients: a systematic review and meta-analysis - Eslam Mohammed Rabea; Mohamed Mohamed Belal; Abdelrahman H. Hafez; Ashraf Hassan Elbanna; Mahmoud Ahmed Khalifa; Anas Zakarya Nourelden; Nada H. Mahmoud; Mohamed Sayed Zaazouee (Acta Neurologica Belgica, 2024)
Background Multiple sclerosis (MS) is a chronic inflammatory, immune-mediated disease affecting the central nervous system. Natalizumab, an FDA-approved monoclonal antibody for MS, has been explored for its off-label extended interval dosing (EID), suggesting a potential reduction in the risk of progressive multifocal leukoencephalopathy (PML) compared to standard interval dosing (SID). Our objective was to assess the efficacy and safety of EID in comparison to SID for natalizumab treatment in patients with MS. Methods We searched PubMed, Embase, WOS, Scopus, Ovid, Science Direct, Clinical trials.gov, and Cochrane Library. Our assessed outcomes were clinical relapses, MRI activity, change in expanded disability status scale [EDSS], and the risk of PML. The EID group was defined as 5 to 8 weeks [EID (Q5-8W)]. The analysis was conducted using RevMan ver. 5.4. The effect estimates were presented as a risk ratio [RR] or mean difference with 95% confidence intervals [CI] using SID group as the reference for comparisons. Results Fourteen studies met our inclusion criteria: 2 RCTs, 1 switched single-arm trial, and 12 observational studies. No significant differences were found in all efficacy outcomes of interest. Risk of clinical relapses [RR = 0.90, (95%CI 0.80, 1.02)], risk of new or newly enlarging T2 hyperintense MRI lesions [RR = 0.78, (95%CI 0.59, 1.04)], risk gadolinium enhancing lesions [RR = 1.30, (95%CI 0.98, 1.72)], change in EDSS [MD = 0.09 (95%CI − 0.57, 0.76)], risk of PML [RR = 1.09, 95%CI (0.24, 4.94)]. Conclusion In summary, our meta-analysis indicates that natalizumab maintains its effectiveness under extended interval dosing [up to 8 weeks], presenting comparable risks for clinical relapses, MRI lesions, EDSS, and PML. Caution is advised given study limitations and heterogeneity. Robust conclusions necessitate well-designed high-quality prospective studies.

Recent advances in electrochemical sensors based on nanomaterials for detection of red dyes in food products: A review - Aya M. Mohamed; Fouad Hassan Fouad; George Raouf Fayek; Kareem Mohsen El Sayed; Mohamed Nabil Ahmed; Raghda Zayed Mahmoud; Rasha M. El Nashar (Food Chemistry, 2024)

Multi-decadal coastal change detection using remote sensing: the Mediterranean coast of Egypt between El-Dabaa and Ras El-Hekma - Esraa A. El-Masry; Asmaa Magdy; Ayman El-Gamal; Baher Mahmoud; Mahmoud Kh. El-Sayed (Environmental Monitoring and Assessment, 2024)
A key source of information for many decision support systems is identifying land use and land cover (LULC) based on remote sensing data. Land conservation, sustainable development, and water resource management all benefit from the knowledge obtained from detecting changes in land use and land cover. The present study aims to investigate the multi-decadal coastal change detection for Ras El-Hekma and El-Dabaa area along the Mediterranean coast of Egypt, a multi-sectoral development area. Besides, the superiority of the area is highly dependent on its proximity to three development projects: the tourism and urban growth pole at Ras El-Hekma, the beachfront Alamain New Mega City, and the Nuclear Power Plant at El Dabaa. This study utilized multi-spectral Landsat satellite images covering 1990, 2010, and 2020 to perceive the post-classification change detection analysis of the land use and land cover changes (LULCC) over 30 years. The results of the supervised classification from 1990 to 2020 showed a 47.33 km 2 (4.13%) expansion of the agricultural land area, whereas the bare soil land area shrunk to 73.13 km 2 (6.24%). On the other hand, the built-up activities in the area launched in 2010 and escalated to 20.51 km 2 (1.77%) in 2020. The change in land use reveals the shift in the economic growth pattern in the last decade toward tourism and urban development. Meanwhile, it indicates that no conflict has yet arisen regarding the land use between the expanded socioeconomic main sectors (i.e., agriculture, and tourism). Therefore, the best practices of land use management and active participation of the stakeholders and the local community should be enhanced to achieve sustainability and avoid future conflicts. An area-specific plan including resource conservation measures and the provision of livelihood alternatives should be formulated within the National Integrated Coastal Zone Management (ICZM) plan with the participation of the main stakeholders and beneficiaries. The findings of the present work may be considered useful for sustainable management and supportive to the decision-making process for the sustainable development of this area.

Efficient utilization of ceramic waste (cyclone dust waste) for enhancing the photocatalytic performance of TiO2 nanoparticles toward Rhodamine B photodegradation - Mahmoud Adel Hamza; Aya El-Sayed; Ayat N. El-Shazly; Maryam G. Elmahgary (Journal of Cleaner Production, 2024)

Molecular mechanism of empagliflozin cardioprotection in 5-fluorouracil (5-FU)-induced cardiotoxicity via modulation of SGLT2 and TNFα/TLR/NF-κB signaling pathway in rats - Marwa Monier Mahmoud Refaie; Sayed Shehata; Maram El-Hussieny; Michael Atef Fawzy; Nagwa Zenhom Mustafa Ahmed; Heba Marey; Asmaa Mohammed Hishmat; Turki Alkully; Eman Shaaban Mahmoud Abd El Rahman (Toxicological Research, 2024)
One of the commoly used chemotherapeutic agents is 5-Fluorouracil (5-FU). Unfortunately, the clinical administration of 5-FU is complicated with serious cardiotoxic effects and the safe use becomes an urgent task in cardio-oncology. Till now, there are no studies discussed the role of empagliflozin (EMP) against 5-FU cardiotoxicity. Thus, we investigated this effect and the involved mechanisms in 5-FU induced heart injury. Forty male rats of Wistar albino species were used and divided randomly into four groups. Group I is the control group, group II is EMP given group, group III is 5-FU cardiotoxic group and group IV is 5-FU plus EMP group. 5-FU (150 mg/kg) was administered as a single intraperitoneal (i.p.) dose on 1st day to induce cardiotoxicity with or without EMP (30 mg/kg/d) orally for 5 days. The dose of 5-FU is relevant to the human toxic dose. Our data showed that 5-FU given group caused cardiotoxicity with significant increase of serum cardiac enzymes, toll like receptors, enhancement of nuclear factor kappa B (NF-κB), interleukin1β (IL1β), IL6, myeloid-differentiation-factor 88 (MYD88), heart weight, malondialdehyde (MDA), tumor-necrosis-factor-alpha (TNFα), sodium glucose co-transporter 2 (SGLT2), P53 and caspase3 expression with clear histopathological features of cardiotoxicity. Moreover, there is a significant decrease in reduced glutathione (GSH) and total antioxidant capacity (TAC). Interestingly, co-administration of EMP could ameliorate 5-FU induced biochemical and histopathological changes. This effect may be due to modulation of SGLT2, decreasing inflammation, oxidative stress and apoptosis with downregulation of an essential inflammatory cascade that mediates 5-FU cardiotoxicity; TNFα/TLR/NF-κB.

Mechanistic aspects of ameliorative effects of Eicosapentanoic acid ethyl ester on methotrexate-evoked testiculopathy in rats - Noha A. T. Abbas; Shaimaa S. El-Sayed; Samaa Salah Abd El-Fatah; Walaa M. Sarhan; Eman M. A. Abdelghany; Omnia Sarhan; Shireen S. Mahmoud (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Disrupted spermatogenesis and testicular injury are among the devastating outcomes of methotrexate. A major contributor to methotrexate-induced testiculopathy is oxidative damage which triggers apoptosis and altered autophagy responses. Eicosapentaenoic acid ethyl ester (EPA-E) is an antihyperlipidemic derivative of omega-3 fatty acids that exhibited affinity to peroxisome proliferator-activated receptor-γ (PPAR-γ) that possesses both antioxidant and autophagy modulating properties. This is an exploratory study aiming at assessing the effectiveness of EPA-E to alleviate testicular damage induced by methotrexate. The specific exploratory hypothesis of this experiment is: EPA-E administration for 1 week to methotrexate-treated rats reduces testicular damage compared to control rats. As a secondary outcome, we were interested in identifying the implicated mechanism that mediates the action of EPA-E. In adult male Wistar rats, testiculopathy was achieved by a single methotrexate injection (20 mg/kg, ip ). Rats received vehicle, EPA-E (0.3 g/kg/day, po ) alone or with selective PPAR-γ antagonist (bisphenol A diglycidyl ether, BADGE) at 30 mg/kg/day, ip for 1 week. EPA-E recuperated methotrexate-attenuated serum total testosterone while reduced testicular inflammation and oxidative stress, restoring superoxide dismutase (SOD) while reducing malondialdehyde (MDA) and 8–hydroxy–2′-deoxyguanosine (8-OHdG). Methotrexate-induced testicular apoptosis (caspase-3 and p53) was suppressed upon EPA-E treatment. Besides, EPA-E curbed methotrexate-induced abnormal autophagy by downregulating LC3A/B and beclin-1. Interestingly, BADGE-coadministration reversed EPA-E beneficial actions. Collectively, our findings suggest PPAR-γ role in EPA-E-mediated mitigation of methotrexate-evoked testiculopathy via suppression of oxidative stress, apoptosis, as well as abnormal autophagy. Furthermore, EPA-E could be used as a preventive therapy for some testiculopathies mediated by oxidative stress. Graphical Abstract

Shoreline displacement along the Mediterranean coast of Egypt between El-Dabaa – Ras El-Hekma - Esraa A. El-Masry; Asmaa Magdy; Baher Mahmoud; Ayman El-Gamal; Mahmoud Kh. El-Sayed (Regional Studies in Marine Science, 2023)

Correction to: Seroprevalence of Rift Valley Fever virus in one‑humped camels (Camelus dromedaries) in Egypt - Mohamed Marzok; Khalid Alkashif; Mahmoud Kandeel; Mohamed Salem; Mohamed Z. Sayed‑Ahmed; Abdelfattah Selim (Tropical Animal Health and Production, 2023)

Improving the productive performance of growing lambs using prebiotic and probiotic as growth promoters - Mohsen Mahmoud Shoukry; Yasser Ahmed Abd El-Fattah El-Nomeary; Fatma Mansour Salman; Waleid Mohamed EL-Sayed Shakweer (Tropical Animal Health and Production, 2023)
The feed additives (prebiotics and probiotics) are used to stabilize the healthy gut microbiome by supporting beneficial microorganisms, thereby improving the animal growth rate. Thirty growing lambs, with around 20.50 ± 0.65 kg live weight were placed into five equal groups (6 animals each). The concentrate feed mixture (CFM) + roughage was given to the control groups. The treatments (T) of T1, T2, and T3 treatments were fed the control ration with three levels of prebiotic supplementation: 0.50, 1.00, and 1.50 g/kg CFM of mannan oligosaccharids + beta glucan, respectively. The T4 received the control ration and was supplemented with 1.0 g/kg CFM probiotic (3.0 × 10 8 CFU/g, Bacillus amyloliquefaciens ). The roughage was provided ad libitum, and the animals were supplemented with CFM at 2.00% of the body weight. A digestibility trial was conducted at the end of the 150-day feeding trial. The results demonstrated that increasing the prebiotic to 0.15% enhanced average daily gain and feed efficiency ( P < 0.05) when compared to the control group. Although daily gain and feed efficiency in probiotic-fed animals were higher ( P < 0.05) than in the control group, they were lower in prebiotic-fed lambs. The blood parameters were within normal range. The animals that received 0.10% prebiotic had the highest economic feed efficiency when compared to the other groups. Prebiotic treatment improved nutrient digestibility and nutritive values; however, the results for control and probiotic treatment were practically identical. Additionally, further research is needed to investigate the effects of prebiotics, probiotics and synbiotics as feed additives on productive and reproductive performance in ruminants.

Comprehensive phytochemical characterization of Persea americana Mill. fruit via UPLC/HR-ESI–MS/MS and anti-arthritic evaluation using adjuvant-induced arthritis model - Dina Atef Waly; Aisha Hussein Abou Zeid; Hanan Naeim Attia; Kawkab A. Ahmed; El-Sayeda Ahmed El-Kashoury; Ali Mahmoud El Halawany; Reda Sayed Mohammed (Inflammopharmacology, 2023)
Persea americana Mill. (avocado fruit) has many health benefits when added to our diet due to various pharmacological activities, such as preventing bone loss and inflammation, modulating immune response and acting as an antioxidant. In the current study, the total ethanol extract (TEE) of the fruit was investigated for in vitro antioxidant and anti-inflammatory activity via DPPH and cyclooxygenase enzyme inhibition. Biological evaluation of the antiarthritic effect of the fruit extract was further investigated in vivo using Complete Freund’s Adjuvant (CFA) arthritis model, where the average percentages of body weight change, inhibition of paw edema, basal paw diameter/weight and spleen index were estimated for all animal groups. Inflammatory mediators such as serum IL-6 and TNF-α were also determined, in addition to histopathological examination of the dissected limbs isolated from all experimental animals. Eighty-one metabolites belonging to different chemical classes were detected in the TEE of P. americana fruit via UPLC/HR-ESI–MS/MS. Two classes of lyso-glycerophospholipids; lyso-glycerophosphoethanolamines and lysoglycerophosphocholines were detected for the first time in avocado fruit in the positive mode. The TEE of fruit exhibited significant antioxidant and anti-inflammatory activity in vitro. In vivo anti-arthritic activity of the fruit TEE improved paw parameters, inflammatory mediators and spleen index. Histopathological findings showed marked improvements in the arthritic condition of the excised limbs. Therefore, avocado fruit could be proposed to be a powerful antioxidant and antiarthritic natural product.

Seed priming with iron oxide nanoparticles improves yield and antioxidant status of garden pea (Pisum sativum L.) grown under drought stress - Muhammad Waqas Mazhar; Muhammad Ishtiaq; Mehwish Maqbool; Fazal Ullah; Shaban R.M. Sayed; Eman A. Mahmoud (South African Journal of Botany, 2023)

Seroprevalence of Rift Valley Fever virus in one-humped camels (Camelus dromedaries) in Egypt - Mohamed Marzok; Khalid Alkashif; Mahmoud Kandeel; Mohamed Salem; Mohamed Z. Sayed-Ahmed; Abdelfattah Selim (Tropical Animal Health and Production, 2023)

Bluetongue virus infection in cattle: serosurvey and its associated risk factors - Abdelfattah Selim; Mohamed Marzok; Khalid Alkashif; Mahmoud Kandeel; Mohamed Salem; Mohamed Z. Sayed-Ahmed (Tropical Animal Health and Production, 2023)

Correction to: Heavy metals in popularly sold branded cigarettes in Bangladesh and associated health hazards from inhalation exposure - Mehedi Hasan; Md Moazzem Hossain; Shaifa Abrarin; Tapos Kormoker; Md Masum Billah; Md Khurshid Alam Bhuiyan; Md Ahedul Akbor; Sayed MA Salam; Rahat Khan; Kamrun Naher; Mohammed Abdus Salam; Mir Mohammad Ali; et al. (Environmental Science and Pollution Research, 2023)

Green hydrogen: Pathways, roadmap, and role in achieving sustainable development goals - A.G. Olabi; Mohammad Ali Abdelkareem; Mohamed S. Mahmoud; Khaled Elsaid; Khaled Obaideen; Hegazy Rezk; Tabbi Wilberforce; Tasnim Eisa; Kyu-Jung Chae; Enas Taha Sayed (Process Safety and Environmental Protection, 2023)

Heavy metals in popularly sold branded cigarettes in Bangladesh and associated health hazards from inhalation exposure - Mehedi Hasan; Md Moazzem Hossain; Shaifa Abrarin; Tapos Kormoker; Md Masum Billah; Md Khurshid Alam Bhuiyan; Md Ahedul Akbor; Sayed M A Salam; Rahat Khan; Kamrun Naher; Mohammed Abdus Salam; Mir Mohammad Ali; et al. (Environmental Science and Pollution Research, 2023)

Hepatic heat shock proteins, antioxidant-related genes, and immunocompetence of heat-stressed broilers in response to short periods of incubation during egg storage and thermal conditioning - Mona A. Hemida; Sayed A. Abdel-Fattah; Mahmoud Madkour; Mohamad M. Aboelenin; Sarah Y.A. Ahmed; Mohamed Shourrap (Journal of Thermal Biology, 2023)

Assessment of Water for Different Uses at Some Localities of the Dakhla Oasis, Western Desert, Egypt - Mahmoud H. Darwish; Asmaa G. Sayed; Sedky H. A. Hassan (Water, Air, & Soil Pollution, 2023)

Novel nanofiltration membrane modified by metal oxide nanocomposite for dyes removal from wastewater - Aya Abd El Aziz Elfiky; Mahmoud F. Mubarak; Mohamed Keshawy; Ibrahim El Tantawy El Sayed; Thanaa Abdel Moghny (Environment, Development and Sustainability, 2023)
This study focuses on the development of a nanocomposite membrane using polyvinyl chloride and nanocellulose@titanium aluminate to effectively filter and adsorb dye from wastewater. Various analytical techniques were used such as FTIR, XRD, SEM, and TGA to characterize the synthesized adsorptive nanocomposite membrane. The thermal and electrical properties of the membrane were measured using a static system. The study investigated the effect of different adsorbent dosages, pH levels, and dye concentrations on the membrane’s adsorption ability. The PVC-NC@TALCM nanocomposite membrane was found to remove 98.6% of MB dye when loaded with 5% titanium aluminate at pH 10. Kinetic and isotherm studies revealed that the adsorption of MB onto the membrane followed pseudo-second-order kinetics and Freundlich isotherms, respectively. The researchers also highlighted the economic and eco-friendly nature of the PVC-NC@TALCM nanocomposite membrane as a viable option for the removal of MB from industrial wastewater.

Removing of cationic dyes using self-cleaning membranes-based PVC/nano-cellulose combined with titanium aluminate - Aya Abd El Aziz Elfiky; Mahmoud F. Mubarak; Mohamed Keshawy; Ibrahim El Tantawy El Sayed; Thanaa Abdel Moghny (Environmental Science and Pollution Research, 2023)
This research used the phase inversion approach to construct polyvinyl chloride nanocellulose@titanium aluminate nanocomposite membranes (PVC/NC@TALCM) to adsorb and filter dye from wastewater. FTIR, XRD, and SEM were used to determine the adsorptive nanocomposite membrane that had been synthesized. The thermal and electrical properties measurements were carried out using a static system. The influence of several adsorbent dosages, pH, and dye concentrations on the nanocomposite membrane’s adsorption ability was investigated. Using a dead-end filtration system, the PVC-NC@TALCM was evaluated as a pressure filtration membrane system. It was found that 98.6% of MB dye was removed by PVC-NC@TALCM membrane, which was loaded with 5% titanium aluminate at pH 10. The kinetic adsorption studies indicated that the adsorption of MB onto the PVC-NC@TALCM nanocomposite membrane obeys pseudo-second-order that indicates the chemosorption process. The isotherm data were described using Freundlich and Langmuir models, and the Freundlich isotherms were shown to be more closely match the experimental data than the Langmuir model. Finally, the PVC-NC@TALCM nanocomposite membrane was economical, environmentally friendly, and self-cleaning.

Umbelliferone potentiates intestinal protective effect of Lactobacillus Acidophilus against methotrexate-induced intestinal injury: Biochemical and histological study - Emad H.M. Hassanein; Fares E.M. Ali; Manal M. Sayed; Amany Refaat Mahmoud; Fatima A. Jaber; Mohamed H. Kotob; Tarek Hamdy Abd-Elhamid (Tissue and Cell, 2023)

Immunostimulant potential of Moringa Oleifera leaves alcoholic extract versus Oregano Essential Oil (OEO) against cyclophosphamide-induced immunosuppression in broilers chicks - Mostafa Abdelgaber Mohamed; Amany Abdelbaky El-Mleeh; Rania Talat Hamad; Ibrahim Said Abu-Alya; Mohamed Hamdy El-Hewaity; Ahmed Ragab Elbestawy; Abdelrahman Mahmoud Elbagory; Ahmed Saber Sayed-Ahmed; Mabrouk Attia Abd Eldaim; Omnia Ibrahim Elshabrawy (Tropical Animal Health and Production, 2023)
The current study was conducted to evaluate the immunoenhancement effect of Moringa oleifera leaves alcoholic extract (MOLE) versus Oregano essential oil (OEO) against cyclophosphamide induced immunosuppression in broilers chicks. A total of a three hundred one-day-old chicks were assigned randomly into three main dietary groups, control, MOLE, and OEO for 14 days. After 14 days the three main experimental groups were subdivided into six groups, control, cyclophosphamide, MOLE, MOLE and Cyclophosphamide, OEO, and OEO and cyclophosphamide. Each group of these six groups was subdivided into three subgroups. Supplementation of broiler chicks with MOLE and OEO for 14 days significantly increased body weight compared to the control group. However, injection of broiler chicks with cyclophosphamide significantly induced body weight loss, impaired immunological response represented by decreasing total leukocytic count, differential leukocytic count, phagocytic activity, phagocytic index, and hemagglutinin inhibition titer for New Castle disease virus, lymphoid organs depletion, and increased the mortality rate. In contrast, supplementation of cyclophosphamide treated chicks with MOLE and OEO significantly reduced cyclophosphamide induced body weight loss and impaired immunological responses, as it showed significant increase in body weight, total leukocytic count, differential leukocytic count, phagocytic activity, phagocytic index, and hemagglutinin inhibition titer for New Castle disease virus, lymphoid organs proliferation, and reduced the mortality rate. This study indicated that MOLE and OEO supplementation ameliorated cyclophosphamide induced body weight loss and impaired immunological responses.

Bioremediation of chlorpyrifos residues using some indigenous species of bacteria and fungi in wastewater - Eman Mohammad Elzakey; Sabha Mahmoud El-Sabbagh; Eman El-Sayed Nour Eldeen; Ibrahim Abdel-Aziz Adss; Atef Mohamed Khedr Nassar (Environmental Monitoring and Assessment, 2023)
Pollutants cause a huge problem for humans, animals, plants, and various ecosystems, especially water resources. Agricultural, domestic, and industrial waste effluents change the water quality and affect living microorganisms. Therefore, the current study aimed to identify possible microorganisms in wastewater as potential bioremediation agents of pesticide residues. Wastewater samples were collected from El-Khairy agricultural drainage, which receives agricultural and domestic wastes. Bacteria and fungi species were isolated as clean cultures. Wastewater samples were analyzed for pesticide residues via gas chromatography-mass spectroscopy (GC–MS) system. Results uncovered the presence of ten pesticides ranging from 0.0817 to 28.162 µg/l, and the predominant pesticide was chlorpyrifos. Along with that, about nine species (3 bacterial and 6 fungal) were relatively efficient in the removal of chlorpyrifos residues up to 2000 µg/l with removal percentages ranging from 24.16 to 80.93% under laboratory conditions. Two bacterial isolates proficiently degraded significant amounts of chlorpyrifos: Bacillus cereus strain PC2 (GenBank accession No. MZ314010) and Streptomyces praecox strain SP1 (GenBank accession No. MZ314009). In-site bacterial and fungal isolates defined in the current study were proficient in cleaning wastewater of chlorpyrifos pesticide residues.

Analysis of the spatial spread of unplanned slum areas in Zagazig City, Egypt, using geographic information systems - Mourad Henane Ramzy Abd-Almalek; Inaam Mahmoud Bandari; Hossam Kotb Al-Sayed; Ahmed Al-Shahat Al-Minshawi (Applied Geomatics, 2023)

Trimetazidine alleviates paclitaxel-induced peripheral neuropathy through modulation of TLR4/p38/NF-κB and klotho protein expression - Asmaa S.A. Hammad; Mohamed M. Sayed-Ahmed; Sara Mohamed Naguib Abdel Hafez; Ahmed R.N. Ibrahim; Mohamed M.A. Khalifa; Mahmoud El-Daly (Chemico-Biological Interactions, 2023)

Hospital and laboratory outcomes of patients with COVID-19 who received vitamin D supplementation: a systematic review and meta-analysis of randomized controlled trials - Mohamed Sayed Zaazouee; Mahmoud Eleisawy; Amira M. Abdalalaziz; Mahmoud M. Elhady; Omar Adel Ali; Taghreed Mohamed Abdelbari; Sara Mohamed Hasan; Hossam Waleed Almadhoon; Alaa Yehia Ahmed; Alaa Shaban Fassad; Rewan Elgendy; Eman Adnan Abdel-Baset; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Coronavirus disease 2019 (COVID-19) has a wide-ranging spectrum of clinical symptoms, from asymptomatic/mild to severe. Recent research indicates that, among several factors, a low vitamin D level is a modifiable risk factor for COVID-19 patients. This study aims to evaluate the effect of vitamin D on hospital and laboratory outcomes of patients with COVID-19. Five databases (PubMed, Embase, Scopus, Web of Science, and Cochrane Library) and clinicaltrials.gov were searched until July 2022, using relevant keywords/Mesh terms. Only randomized clinical trials (RCTs) that addressed the topic were included. The Cochrane tool was used to assess the studies’ risk of bias, and the data were analyzed using the review manager (RevMan 5.4). We included nine RCTs with 1586 confirmed COVID-19 patients. Vitamin D group showed a significant reduction of intensive care unit (ICU) admission (risk ratio = 0.59, 95% confidence interval (CI) [0.41, 0.84], P = 0.003), and higher change in vitamin D level (standardized mean difference = 2.27, 95% CI [2.08, 2.47], P < 0.00001) compared to the control group. Other studied hospital and laboratory outcomes showed non-significant difference between vitamin D and the control group ( P ≥ 0.05). In conclusion, vitamin D reduced the risk of ICU admission and showed superiority in changing vitamin D level compared to the control group. However, other outcomes showed no difference between the two groups. More RCTs are needed to confirm these results.

Assessing the efficacy of un and gamma-irradiated entomopathogenic nematode, Steinernema carpocapsae as an eco-friendly approach to control Agrotis ipsilon larvae - Rehab Mahmoud Sayed; Tammy Samir El Sayed; Salwa Abdou Rizk (International Journal of Tropical Insect Science, 2023)
The black cutworm, Agrotis ipsilon (Hufnagel) is one of the most devastating agricultural pests that attack different crops worldwide. Entomopathogenic nematodes (EPNs) have been utilized in classical, conservation, and augmentative biological control programs. Consequently, this study was designed to estimate the efficacy of an unirradiated and gamma-irradiated entomopathogenic nematode, Steinernema carpocapsae (all), against A. ipsilon larvae as a safe control tool to reduce chemical environmental hazards. The virulence of different concentrations (10, 20, 30 and 40 IJs/ml) of unirradiated and gamma-irradiated (with 2 Gy) of S. carpocapsae was evaluated. Changes in peroxidase (Px) and polyphenyl oxidase (PPO) zymographic patterns were also investigated after larvae were treated with LC 50 values for S. carpocapsae. The results revealed that larval mortality increased with increasing S. carpocapsae concentration and time after treatment. The 2 Gy gamma-irradiated S. carocapsae caused a greater pathogenic effect than the unirradiated S. carocapsae , where the LC 50 values of 2 Gy gamma-irradiated S. carocapsae were 31.19 and 17.78 IJs/ml after 1 and 2 days, respectively, compared to 113.23 and 65.83 IJs/ml for unirradiated S. carocapsae . For the toxicity index, gamma irradiation at a dose of 2 Gy was selected and given an arbitrary 100 units and considered a standard treatment. Analysis of gel electrophoresis revealed 3 bands of Px and PPO in control larvae; treatment with unirradiated and irradiated S. carpocapsae caused the disappearance of the first band of both enzymes and lowered the intensity of the other 2 bands. The laboratory studies revealed that 2 Gy gamma-irradiated S. carpocapsae could be used as an eco-safe management tool against A. ipsilon larvae under field conditions.

Characterization of ZnO and Mn-doped ZnO nanoparticles and their antimicrobial activity - Yasser Fathy Abdelaliem; Tarob Abdel-Naby Abdel-Baset; Alaa Ropy Mahmoud Sayed; Aya Ahmed Owis; Mohamed Fawzy Ramadan; Adel Abdelrazek Abdelazim Mohdaly (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

New tetracyclic systems integrated thienopyridine scaffold as an anti-dementia lead: in silico study and biological screening - Zeinab Mahmoud; Lamia W. Mohamed; Khaled O. Mohamed; Hadeer S. Sayed; May A. Abd El Fattah; Afaf El-Malah (Medicinal Chemistry Research, 2023)
Alzheimer’s disease (AD) is a multifactorial incurable neurodegenerative disorder. To date, cholinesterase inhibitors (ChEI) are the mainstay line of treatment to ameliorate the symptoms of AD. Tacrine and donepezil are considered two important cornerstones of anti-dementia drugs. Accordingly, novel series of hexahydrobenzothienocyclopentapyridines, octahydrobenzo-thienoquinolines, hexahydrocyclopenta(thienoquinoline/thienodipyridine), and octahydropyrido-thienoquinolines were efficiently synthesized from readily available reagent, e.g. cyclohexanones, cyclopentanone, and 1-methyl-piperidin-4-one to afford 14 new compounds. All new compounds were screened against their acetylcholinesterase, butyrylcholinesterase, and β-amyloid protein inhibition. In AChE inhibition assay, compound 3,7-dimethyl-1,2,3,4,7,8,9,10-octahydrobenzo[4,5]thieno[2,3- b ]quinolin-11-amine ( 2h ) showed IC 50 value 9.24 ± 0.01 μM × 10 −2 excelling tacrine. Compound 1,7-dimethyl-1,2,3,4,7,8,9,10-octahydrobenzo[4,5]thieno[2,3- b ]quinolin-11-amine ( 2e ) possess excellent IC 50 values 0.58 ± 0.02 μM × 10 −2 and 0.51 ± 0.001 μM × 10 −4 for both butyrylcholinesterase and β-amyloid protein inhibition assays, sequentially. In silico ADME studies were investigated for the promising members (octahydrobenzo-thienoquinolines 2c , 2d , 2e , 2h , 2i , and octahydropyrido-thienoquinolines 4e ) and all the results were illustrated. A comparative docking study was conducted between the promising members and both tacrine and donepezil in both acetyl and butyryl choline active sites. The results revealed extra binding patterns and good agreement with the biological results.

Potential Symbiotic Effects of β-1,3 Glucan, and Fructooligosaccharides on the Growth Performance, Immune Response, Redox Status, and Resistance of Pacific White Shrimp, Litopenaeus vannamei to Fusarium solani Infection - El-Sayed Hemdan Eissa; Ragaa A. Ahmed; Nadia A. Abd Elghany; Amal Elfeky; Saadea Saadony; Norhan H. Ahmed; Salah El-Sayed Sakr; Geraldine B. Dayrit; Charlene Princess S. Tolenada; Adlene Anne C. Atienza; Mahmoud Mabrok; Hala F. Ayoub (Fishes, 2023)
The potential effects of dietary supplementation with β-1,3 glucan and fructooligosaccharides (β-1,3 GF) on antioxidant activities, immunological response, and growth performance of Pacific white shrimp (Litopenaeus vannamei) was investigated. Four diets (iso-energetic and iso-nitrogenous) with different levels of β-1,3 GF (0, 0.5, 1.0, and 1.5 g kg−1) were fed to healthy shrimp juveniles weighing 3 ± 0.5 g for 75 days. Shrimps were randomly distributed into 12 net enclosures at a density of 30 shrimp/net, and the experiment was performed in triplicate. The results revealed that long-term supplementation with 1.5 g kg−1 β-1,3 GF significantly improved shrimp weight gain, feed conversion ratio, and digestive enzyme profiles compared to the control diet group. However, there were no substantial variations in the contents of moisture, crude protein, total lipids, and ash in the muscles of shrimp fed on different diets. Surprisingly, all antioxidants (superoxide dismutase, catalase, glutathione peroxidase) and immune biomarkers (lysozyme, total hemocyte count, phenol oxidase, and respiratory burst) activities were significantly elevated with increasing levels of β-1,3 GF in the shrimp diet, and the highest values were recorded in the 1.5 g kg−1 diet groups. Challenge test results revealed that F. solani could cause a high mortality rate (86.7%) in a group fed a normal basal diet within 14 days at a dose of 5 × 104 conidia mL−1. Surprisingly, all dietary treated groups with different doses of β-1,3 GF showed high resistance against F. solani, represented by lower cumulative mortality rates (20–43.3%) compared to the control group. Moreover, most of the infected shrimp showed a typical black to brown gill lesion similar to that observed in the natural infection, where an identical fungus was successfully re-isolated from infected gills and muscles. Overall, this study recommends an appropriate incorporation level of β-1,3 GF that could enhance growth performance and improve the antioxidant activities, non-specific immunity, and disease resistance of L. vannamei, with an optimal level of 1.5 g kg−1.

Protective efficacy of Eglin C from Hirudo medicinalis against Eimeria papillata-induced coccidiosis - Shrouk E. Al-Sayed; Mahmoud Abdel-Latif; Heba M. Abdel-Haleem; Gamal El-Shahawy; Heba Abdel-Tawab (Veterinary Parasitology, 2023)

An overview on the progress in produced water desalination by membrane-based technology - Nur'Aishah Ahmad Shahrim; Nada Mahmoud Abounahia; Aya Mohammed Ahmed El-Sayed; Haleema Saleem; Syed Javaid Zaidi (Journal of Water Process Engineering, 2023)

Multi-functional of TiO2@Ag core–shell nanostructure to prevent hydrogen sulfide formation during anaerobic digestion of sewage sludge with boosting of bio-CH4 production - Gamal K. Hassan; Walaa H. Mahmoud; Aly Al-sayed; Sameh H. Ismail; Ahmed A. El-Sherif; S.M. Abd El Wahab (Fuel, 2023)

Vitamin D ameliorates diethylnitrosamine-induced liver preneoplasia: A pivotal role of CYP3A4/CYP2E1 via DPP-4 enzyme inhibition - Hebatollah E. Eitah; Hanan Naeim Attia; Ahmed A.F. Soliman; Amina A. Gamal el Din; Khaled Mahmoud; Rabab H. Sayed; Yousreya A. Maklad; Ayman E. El-Sahar (Toxicology and Applied Pharmacology, 2023)

Genome centric engineering using ZFNs, TALENs and CRISPR-Cas9 systems for trait improvement and disease control in Animals - Atif Khurshid Wani; Nahid Akhtar; Reena Singh; Ajit Prakash; Sayed Haidar Abbas Raza; Simona Cavalu; Chirag Chopra; Mahmoud Madkour; Ahmed Elolimy; Nesrein M. Hashem (Veterinary Research Communications, 2023)

Oil Spill Identification based on Dual Attention UNet Model Using Synthetic Aperture Radar Images - Amira S. Mahmoud; Sayed A. Mohamed; Reda A. El-Khoriby; Hisham M. AbdelSalam; Ihab A. El-Khodary (Journal of the Indian Society of Remote Sensing, 2023)
Oil spills cause tremendous damage to marine, coastal environments, and ecosystems. Previous deep learning-based studies have addressed the task of detecting oil spills as a semantic segmentation problem. However, further improvement is still required to address the noisy nature of the Synthetic Aperture Radar (SAR) imagery problem, which limits segmentation performance. In this study, a new deep learning model based on the Dual Attention Model (DAM) is developed to automatically detect oil spills in a water body. We enhanced a conventional UNet segmentation network by integrating a dual attention model DAM to selectively highlight the relevant and discriminative global and local characteristics of oil spills in SAR imagery. DAM is composed of a Channel Attention Map and a Position Attention Map which are stacked in the decoder network of UNet. The proposed DAM-UNet is compared with four baselines, namely fully convolutional network, PSPNet, LinkNet, and traditional UNet. The proposed DAM-UNet outperforms the four baselines, as demonstrated empirically. Moreover, the EG-Oil Spill dataset includes a large set of SAR images with 3000 image pairs. The obtained overall accuracy of the proposed method increased by 3.2% and reaches 94.2% compared with that of the traditional UNet. The study opens new development ideas for integrating attention modules into other deep learning tasks, including machine translation, image-based analysis, action recognition, and speech recognition.

Hemato-biochemical indices alteration, oxidative stress, and immune suppression in the African catfish (Clarias gariepinus) exposed to metformin - Hesham Taher; Mahmoud S. Sabra; Alaa El-Din Salah El-Din; Alaa El-Din H. Sayed (Toxicology and Environmental Health Sciences, 2022)

Polyethylene microplastics increases the tissue damage caused by 4-nonylphenol in the common carp (Cyprinus carpio) juvenile - Esraa Ammar; Mahmoud S. Mohamed; Alaa El-Din H. Sayed (Frontiers in Marine Science, 2022)
Plastic particles have the ability to transfer harmful chemical pollutants due to their high adsorption capacity. Therefore, this study aimed to investigate the effects of combined exposure to polyethylene microplastics (PE-MPs) and 4-nonylphenol (4-NP) on juvenile common carp ( Cyprinus carpio ) using histopathological and histochemical biomarkers. Fish were separated into a control group and three treatment groups (10 mg/L PE-MPs; 10 mg/L PE-MPs + 200 µg/L 4-NP; 200 µg/L 4-NP) for a two-week continuous exposure experiment followed by two weeks of recovery. The three treatment groups showed histopathological changes compared to the control. These alterations included severe edema, lifting of the outer epithelium, interlamellar fusion and vacuolation, secondary lamellar shortening and complete fusion, increased mucous cell numbers in the gill tissue, enlargement of inner layer stratum periventricular, cell degeneration with pyknotic nuclei, increased blood capillaries, spongiosis in the brain tissue (optic tectum), central vein hemorrhage, shrunken and fatty degeneration of hepatocytes, rosette shapes around small congested blood sinusoids, vacuoles, necrosis, and severe glycogen reduction in the liver tissue. Some tissue changes improved during the two-week recovery period but did not return to normal. In conclusion, the mixture exposure of the PE-MPs and 4-NP on fish carp induced some histological alterations in most studied tissues and post-exposure made improvement in cellular and tissue structure.

Development of new donepezil analogs: synthesis, biological screening and in silico study rational - Zeinab Mahmoud; Hadeer S. Sayed; Lamia W. Mohamed; Khaled O. Mohamed (Medicinal Chemistry Research, 2022)
Fifteen new benzothiophene-based compounds were designed, synthesized, and evaluated as potential anti-Alzheimer agents. Most of the synthesized compounds exhibited remarkable AChE inhibitory activity and effectively inhibited self-mediated β-amyloid protein in vitro. Compound 3g (IC 50 = 72.488 ± 3.69 μM) showed a significant β-amyloid inhibitory effect exceeding that of donepezil (IC 50 = 87.414 ± 4.46 μM). Furthermore, compound 3j (IC 50 = 0.498 ± 0.02 μM) showed the best inhibitory activity comparable to that of donepezil (IC 50 = 0.404 ± 0.03 μM). The in vivo evaluation of the promising compounds ( 3g and 3j ) confirmed a significant memory improvement in scopolamine-induced memory impairment model in mice. The molecular docking simulation of compounds 3g and 3j in Torpedo californica- AChE ( Tc AChE) active site showed a good agreement with the obtained screening results. The in silico ADMET and other physicochemical parameters were also reported.

Combined Effect of Prickly Pear Waste Biochar and Azolla on Soil Fertility, Growth, and Yield of Roselle (Hibiscus sabdariffa L.) Plants - Hassan M. Al-Sayed; Ahmed M. Ali; Mahmoud A. Mohamed; Mostafa F. Ibrahim (Journal of Soil Science and Plant Nutrition, 2022)
Although the use of biochar to promote plant growth has been reported by many researchers, the combined effect of prickly pear waste biochar (BC) and Azolla (AZ) in a field experiment on the roselle plants did yet receive attention. Therefore, the study aims to evaluate the effect of biochar and Azolla extract on the growth, production, and quality of roselle plants. The experiment treatments were in a completely randomized block design with three replicates. Biochar was added at rates of 0, 10, and 20 ton ha −1 and AZ was applied at rates of 0, 3, and 6% in addition to a control treatment. Biochar added at high rate (20 ton ha −1 ) significantly increased the fresh and dry weights of sepals by 27.98 and 35.73%, respectively, compared to the control. The corresponding values were significantly increased by 11.89 and 11.85% over the control when Azolla was added at rate of 6%. The interaction effect of both BC and AZ treatments at high rate significantly increased the fresh and dry weight of sepals by 47.16 and 60.59%, respectively, compared to the control. The interaction effect of BC and AZ realized significant effect on soil properties, growth and yield, as well as pigments of roselle plants. This is a good evident means that BC and AZ applications separately or combined are considered promising materials for sustainable organic agriculture and safety food.

Physiological and morphological response of tomato plants to nano-chitosan used against bio-stress induced by root-knot nematode (Meloidogyne incognita) and Tobacco mosaic tobamovirus (TMV) - Mohamed Salah Khalil; Mahmoud Hamdy Abd El-Aziz; Rasha El-Sayed Selim (European Journal of Plant Pathology, 2022)
Root-knot nematodes ( Meloidogyne spp.) have been reported to be responsible for large economic losses of agricultural crops due to their wide host range and variety of suitable climates. The control measures of these parasitic nematodes depend upon synthetic nematicides and a small number bio-based products. Chemical nematicides are eliciting adverse effects on the environment and human health. In the present study, an alternative tool, nano-chitosan was tested for the control the root-knot nematodes, Meloidogyne incognita , and Tobacco mosaic tobamovirus (TMV) in greenhouse-cultivated tomato. The effect of nano-chitosan on morphological (weight and length of shoot and root systems) and biochemical responses (Polyphenol oxidase, Peroxides, Total soluble phenol and Total protein) was assessed. The obtained results indicated that densities of Meloidogyne incognita alone or in the presence of TMV were decreased by nano-chitosan at a range of 45.89 to 66.61%, while root gall desntiy was reduced between 10.63 and 67.87%. Moreover, the density of TMV on tomato leaves singly or in the presence of M. incognita was suppressed at range of 10.26 to 65.00% after 20 days of infection, and reached up to 58.00% after 40 days of infection. However, soil application of nano-chitosan pre infection reduced TMV density only by 5.48%. Morphogenesis of tomato plants such as shoot and root systems were significantly improved. The impacts of nano-Chitosan applications on total soluble phenol, total protein, polyphenol oxidase and peroxides after 20 and 40 days of infections varied.

Geoelectric and mineralogical studies for foundation soil characterization in new Luxor city, Upper Egypt - Sayed Omer Elkhateeb; Wael Dosoky; Abdelnasser Mohamed; Mahmoud A. Abbas (Arabian Journal of Geosciences, 2022)
The new Luxor city was proposed by the Egyptian government as a new constructional and building site in order to face the increasing population density around the two banks of the river Nile. It is important prior construction of buildings to characterize the foundation soil. So, vertical electrical resistivity survey and mineralogical investigation were conducted for this purpose. The results obtained from the interpretation of the sounding data indicate that the lithological succession of the study area consists of four geoelectric layers. The top layer corresponds to the surface loose sediments of conglomerate, gravel, and sand. The second geoelectric layer is composed of sand and gravel. The third layer is composed of silty clay, sandy clay, and clayey sand. The fourth geoelectric layer is composed of dry sandstone. The X-ray diffraction (XRD) results of samples collected from the clay-rich layer revealed the presence of smectite mineral as predominate clay minerals which is characterized by its swell potentiality on wetting. Accordingly, the clay zone recorded within the third layer must be taken into consideration during designing the foundations at new Luxor city especially this layer was located at shallow depth range between 1.6 and 7.5 m and attains a relatively big thickness that reach up to 33.5 m in some parts. This study emphasizes the importance of the integration of geophysical investigation and mineralogical analysis of the foundation soil for optimal characterization of a site.

Waste nanomaterial-modified asphalt for economic and sustainable pavement construction - Ali Y. Aboelmagd; Safwan Khedr; Ghada S. Moussa; El-Sayed M. Abdalla; Mahmoud Enieb (Innovative Infrastructure Solutions, 2022)

“Anosmia” the mysterious collateral damage of COVID-19 - Abdulrahman K. Ahmed; Reem Sayad; Islam A. Mahmoud; Aya M. Abd EL-Monem; Salma H. Badry; Islam H. Ibrahim; Mahmoud HR Hafez; Mohamed A. El-Mokhtar; Ibrahim M. Sayed (Journal of NeuroVirology, 2022)

Chloride-binders and their effect on the physico-mechanical properties of sulfate-resisting cement (SRC) hardened pastes upon exposure to sea water attack - Mai M. Yousef; Hamdy A. El-Sayed; Ayman M. Kandeel; Mahmoud Gharieb; Ayman A. Abdel Aziz (Environmental Science and Pollution Research, 2022)

Bioethanol production from defatted biomass of Nannochloropsis oculata microalgae grown under mixotrophic conditions - Nashwa A. H. Fetyan; Abo El-Khair B. El-Sayed; Fatma M. Ibrahim; Yasser A. Attia; Mahmoud W. Sadik (Environmental Science and Pollution Research, 2022)

Vulnerability of tourism to climate change on the Mediterranean coastal area of El Hammam–EL Alamein, Egypt - Esraa A. El-Masry; Mahmoud Kh. El-Sayed; Mohamed A. Awad; Amr A. El-Sammak; Mohamed A. El Sabarouti (Environment, Development and Sustainability, 2022)

Silver nanoparticles as a viricidal agent to inhibit plant-infecting viruses and disrupt their acquisition and transmission by their aphid vector - Ahmed Y. El Gamal; Mohamed R. Tohamy; Mohamed I. Abou-Zaid; Mahmoud M. Atia; Tarek El Sayed; Khaled Y. Farroh (Archives of Virology, 2022)

Olfactory Disturbances as Presenting Manifestation Among Egyptian Patients with COVID-19: Possible Role of Zinc - Aida A. Abdelmaksoud; Ali A. Ghweil; Mohammed H. Hassan; Alaa Rashad; Ashraf Khodeary; Zaky F. Aref; Mennatallah Ali Abdelrhman Sayed; Mahmoud K. Elsamman; Shamardan E. S. Bazeed (Biological Trace Element Research, 2021)

Structural analyses and geological studies of the Late Precambrian Basement Complex in Wadi Faliq El Sahl–Faliq El Waar area, North Eastern Desert, Egypt - El-Sayed Soliman El-Wakel; Hassan Ismail El-Sundoly; Mohamed Mohamed El-Sayed; Mahmoud Hani Shalaby (Arabian Journal of Geosciences, 2021)

4-Nonylphenol induced brain damage in juvenile African catfish (Clarias garepinus) - Zainab Eid; Usama M. Mahmoud; Imam A. A. Mekkawy; Hanem S. Abdel-Tawab; Alaa El-Din H. Sayed (Toxicology and Environmental Health Sciences, 2021)

Seismic response evaluation of structures on improved liquefiable soil - Ayman Abd-Elhamed; Sayed Mahmoud (European Journal of Environmental and Civil Engineering, 2021)

Seismic performance of high-rise buildings in selected regions in Saudi Arabia according to different seismic codes - Sayed Mahmoud; Mohamed Alsearheed; Waleed Abdallah (Earthquake Engineering and Engineering Vibration, 2021)

Synthesis of core–shell activated carbon/CaO composite from Ficus Nitida leaves, as an efficient adsorbent for removal of methylene blue - Mostafa M. Emara; Rabie Saad Farag; Mahmoud F. Mubarak; Sayed Kotb Ali (Nanotechnology for Environmental Engineering, 2020)

Geo-Environmental Changes and Their Impact on the Development of the Limestone Plateau, West of Assiut, Egypt - Mahmoud H. Darwish; Hanaa A. Megahed; Abd El-Hay A. Farrag; Asmaa G. Sayed (Journal of the Indian Society of Remote Sensing, 2020)

Biosurfactant electrospun nanofibers exhibit minimal side effects on the structure and function of the liver tissue in male rat model - Hossam Abd Rabou Ebaid; Ahmed Abdel-Mageed; Jameel Homoud Al-Tamimi; Iftekhar Hassan; Ahmed Mostafa Rady; Mohamed Hassan El-Newehy; Ashraf Mohamed Mashaly; Ahmed AbdelFattah Mahmoud Abdel-Megeed; Ibrahim Alhazza; Essam Sayed Abdel-Halim; Abdelfattah Zeidan Mohamed Salem (Environmental Science and Pollution Research, 2020)

17β-Estradiol augments the neuroprotective effect of agomelatine in depressive- and anxiety-like behaviors in ovariectomized rats - Yasmine A. El-Khatib; Rabab H. Sayed; Nada A. Sallam; Hala F. Zaki; Mahmoud M. Khattab (Psychopharmacology, 2020)

Petrology of Early Paleogene phosphorite deposits in Hazm Al-Jalamid, Northwest Saudi Arabia - Mahmoud Ahmed Galmed; Mahmoud Moselhi Nasr; Ashraf El-Sayed Mohamady Khater (Arabian Journal of Geosciences, 2020)

Polystyrene-based magnetic hydrogels for elimination of some toxic metal cations from aqueous solutions - Mohamed Keshawy; Abdul-Raheim Mahmoud; Manar El-Sayed Abdel-Raouf (Environmental Science and Pollution Research, 2020)

Risk assessments and spatial distributions of natural radioactivity and heavy metals in Nasser Lake, Egypt - Noha Imam; Seliem Mahmoud El-Sayed; Mohamed El-Sherif Goher (Environmental Science and Pollution Research, 2020)

Osteoblast-Based Therapy—A New Approach for Bone Repair in Osteoporosis: Pre-Clinical Setting - Nadia Samy Mahmoud; Mohamed Ragaa Mohamed; Mohamed Ahmed Mohamed Ali; Hadeer Ahmed Aglan; Khalda Sayed Amr; Hanaa Hamdy Ahmed (Tissue Engineering and Regenerative Medicine, 2020)

Geology and evolutionary stages of the Late Precambrian Hammamat sediments at Gebel Um Tawat, North Eastern Desert, Egypt - Asmaa Adel Khalifa; Hossam Anwer Khamis; Mohamed Mohamed El-Sayed; Mahmoud Hany Shalaby (Arabian Journal of Geosciences, 2020)

An integrated water quality assessment of Damietta and Rosetta branches (Nile River, Egypt) using chemical and biological indices - Seleim M. El Sayed; Mahmoud H. Hegab; Hesham R. A. Mola; Nasr M. Ahmed; Mohame E. Goher (Environmental Monitoring and Assessment, 2020)

Significance Assessment of Amphora coffeaeformis in Arsenic-Induced Hemato- Biochemical Alterations of African Catfish (Clarias gariepinus) - Imam A. Mekkawy; Usama M. Mahmoud; Rehab H. Moneeb; Alaa El-Din H. Sayed (Frontiers in Marine Science, 2020)

Silver nanoparticle–induced nephrotoxicity in Clarias gariepinus: physio-histological biomarkers - Usama M. Mahmoud; Imam A. A. Mekkawy; Mervat Naguib; Alaa El-Din H. Sayed (Fish Physiology and Biochemistry, 2019)

Mapping of lineaments for groundwater assessment in the Desert Fringes East El-Minia, Eastern Desert, Egypt - Alaa Ahmed; Mahmoud El Ammawy; Abdel Galil Hewaidy; Bothaina Moussa; Nabil Abdel Hafz; El Sayed El Abd (Environmental Monitoring and Assessment, 2019)

Using ZnO nanoparticles in fungal inhibition and self-protection of exposed marble columns in historic sites - Mohammad Ateeq Aldosari; Sawsan S. Darwish; Mahmoud A. Adam; Nagib A. Elmarzugi; Sayed M. Ahmed (Archaeological and Anthropological Sciences, 2019)

Evaluation of preventive performance of kaolin and calcium hydroxide nanocomposites in strengthening the outdoor carved limestone - Mohammad A. Aldosari; Sawsan S. Darwish; Mahmoud A. Adam; Nagib A. Elmarzugi; Sayed M. Ahmed (Archaeological and Anthropological Sciences, 2019)

Prevalence and distribution pattern of intestinal helminths in chicken and pigeons in Aswan, Upper Egypt - Khaled Mohamed El-Dakhly; Mahmoud A. El-Seify; Eman Sayed Mohammed; Ismail Saad Elshahawy; Samia Abdel-Motaleb Fawy; Mossab A. Omar (Tropical Animal Health and Production, 2019)

Preparation and Using Modified Nanohydroxyapatite Molecules for Wastewater Treatment - Mohamed E. A. El-Sayed; Atef F. Ahmed; Othman A. Farghaly; M. Abd-Elmottaleb; Tarek A. Seaf Elnasr; Mahmoud A. M. Hassan (Water Conservation Science and Engineering, 2018)

Trichosporon jirovecii infection of red swamp crayfish ( Procambarus clarkii ) - Ebtsam Sayed Hassan Abdallah; Mahmoud Mostafa Mahmoud; Ismail Ramadan Abdel‐Rahim (Journal of Fish Diseases, 2018)
One hundred and twenty‐nine isolates of Trichosporon jirovecii were isolated from the melanized exoskeleton as well as eyestalks, gills, muscle and haemolymph of red swamp crayfish ( Procambarus clarkii ) collected from the River Nile, during summer 2015. Isolates were similar morphologically, biochemically and genetically. Also, random amplified polymorphic DNA (RAPD) analysis exhibited no polymorphism among the tested isolates. Virulence factors such as chitinase, protease, lipase activities and biofilm formation were examined. Challenge test, using a representative isolate (Tj_ASU8), proved its pathogenicity against crayfish. Magnesium oxide nanoparticles had a good antifungal activity with a minimum fungicidal concentration of 8 mg/ml. To the best of our knowledge, this is the first report for isolation of T. jirovecii from red swamp crayfish, showing melanization, from the River Nile. We assume that infected crayfish may act as a vector for this fungus and can disseminate infection to all susceptible hosts in the vicinity.

Aberrant Expression of Some Circulating miRNAs in Childhood Acute Lymphoblastic Leukemia - Menha Swellam; Maha Hashim; Magda Sayed Mahmoud; Amal Ramadan; Naglaa M. Hassan (Biochemical Genetics, 2018)

Hepatotoxic responses of 4-nonylphenol on African catfish (Clarias gariepinus): antixoidant and histochemical biomarkers - Mahmoud Abd-Elkareem; Nasser S. Abou Khalil; Alaa H. Sayed (Fish Physiology and Biochemistry, 2018)

Teratogenic effects induced by chitosan oligosaccharide in Wistar female rat Rattus norvegicus - Amal Abdel Aziz Eisa; Gamal El-Sayed Aboelghar; Ibrahim Mahmoud Ammar; Hala Gabr Metwally; Samah Saied Arafa (Environmental Science and Pollution Research, 2018)

Physical characteristics of heat-dissipating smart marble at Al Masjid Al-Haram, Makkah City, Saudi Arabia - Ahmed Abdel Aal; Hamada Shoukry; Mahmoud A. Sayed; Hamed A. Ghramh (Arabian Journal of Geosciences, 2018)

Combined QM/MM and Monte Carlo study for redox leveling in Mn and Fe superoxide dismutase - Muhamed Amin; Zainab Mohamed; Mohamed El-Sayed; Asmaa Samy; Afnan Sultan; Mahmoud Bassuoni; Mohamed H. Alkordi (JBIC Journal of Biological Inorganic Chemistry, 2018)

Comparative therapeutic effect of steroidal and non-steroidal anti-inflammatory drugs on pro-inflammatory cytokine production in water buffalo calves (Bubalus bubalis) naturally infected with bronchopneumonia: a randomized clinical trial - Mohamed Abdo Rizk; Motamed Elsayed Mahmoud; Shimaa Abd El-Salam El-Sayed; Doaa Salman (Tropical Animal Health and Production, 2017)

Phytochemical remedies: a key strategy towards reversing the aggressive murine colon cancer - Naglaa A. Attia; Alaa H. Sayed; Nadia S. Mahmoud; Hanaa H. Ahmed (Medicinal Chemistry Research, 2017)

Dietary Supplementation of Chromium Can Alleviate Negative Impacts of Heat Stress on Performance, Carcass Yield, and Some Blood Hematology and Chemistry Indices of Growing Japanese Quail - Mohamed Soliman El-Kholy; Mohamed Mohamed El-Hindawy; Mahmoud Alagawany; Mohamed Ezzat Abd El-Hack; Sabry Abd El-Gawad Abd El-Halim El-Sayed (Biological Trace Element Research, 2017)

Selectivity Improvement for Spectrofluorimetric Determination of Oseltamivir Phosphate in Human Plasma and in the Presence of Its Degradation Product - Mahmoud A. Omar; Sayed M. Derayea; Islam M. Mostafa (Journal of Fluorescence, 2017)

Laser Performance of Some Oxazole Laser Dyes in Restricted Matrices - Mahmoud A. S. Sakr; Sayed A. Abdel Gawad; Maram T. H. Abou Kana; El-Zeiny M. Ebeid (Journal of Fluorescence, 2017)

Detection and characterization of hepatitis A virus circulating in Egypt - Hazem Hamza; Dina Nadeem Abd-Elshafy; Sayed A. Fayed; Mahmoud Mohamed Bahgat; Nagwa Abass El-Esnawy; Emam Abdel-Mobdy (Archives of Virology, 2017)

The effectiveness of dietary sunflower meal and exogenous enzyme on growth, digestive enzymes, carcass traits, and blood chemistry of broilers - Mahmoud Alagawany; Adel I. Attia; Zenat A. Ibrahim; Reda A. Mahmoud; Sabry A. El-Sayed (Environmental Science and Pollution Research, 2017)

Bioactive/Natural Polymeric Scaffolds Loaded with Ciprofloxacin for Treatment of Osteomyelitis - Amany A. Mostafa; Mayyada M. H. El-Sayed; Azza A. Mahmoud; Amira M. Gamal-Eldeen (AAPS PharmSciTech, 2017)

Selective Spectrofluorimetric Method with Enhanced Sensitivity for Determination of Silodosine in Dosage Form and Human Plasma. Application to Stability Studies and Content Uniformity Testing - Mahmoud A. Omar; Abdel-Maaboud I. Mohamed; Sayed M. Derayea; Mohamed A. Hammad; Abobakr A. Mohamed (Journal of Fluorescence, 2017)

Rutin Attenuates Carfilzomib-Induced Cardiotoxicity Through Inhibition of NF-κB, Hypertrophic Gene Expression and Oxidative Stress - Faisal Imam; Naif O. Al-Harbi; Mohammed M. Al-Harbia; Hesham M. Korashy; Mushtaq Ahmad Ansari; Mohamed M. Sayed-Ahmed; Mahmoud N. Nagi; Muzaffar Iqbal; Md. Khalid Anwer; Imran Kazmi; Muhammad Afzal; Saleh Bahashwan (Cardiovascular Toxicology, 2017)

Linking of adjacent three-storey buildings for mitigation of structural pounding during earthquakes - Robert Jankowski; Sayed Mahmoud (Bulletin of Earthquake Engineering, 2016)

Interleukin 28B.rs12979860 genotype does not affect hepatitis C viral load in Egyptians with genotype 4 chronic infection - Sayed F. Abdelwahab; Zainab Zakaria; Walaa R. Allam; Shaimaa Hamdy; Mohamed A. Mahmoud; Maha Sobhy; Eman Rewisha; Imam Waked (Archives of Virology, 2015)

Differential distribution of IL28B.rs12979860 single-nucleotide polymorphism among Egyptian healthcare workers with and without a hepatitis C virus-specific cellular immune response - Sayed F. Abdelwahab; Zainab Zakaria; Maha Sobhy; Shaimaa Hamdy; Mohamed A. Mahmoud; Nabiel Mikhail; Walaa R. Allam; Eman Rewisha; Imam Waked (Archives of Virology, 2015)

In-vitro release and in-vivo performance of tolmetin from different topical gel formulations - Sayed Hassan Auda; Saleh Abd El-Rasoul; Mahmoud Mohamed Ahmed; Shaaban Khalaf Osman; Mahmoud El-Badry (Journal of Pharmaceutical Investigation, 2015)

Novel indolyl-pyrimidine derivatives: synthesis, antimicrobial, and antioxidant evaluations - Mosaad Sayed Mohamed; Mahmoud Moustafa Youns; Naglaa Mohamed Ahmed (Medicinal Chemistry Research, 2014)

In vitro anti-nitrosative, antioxidant, and cytotoxicity activities of plant flavonoids: a comparative study - Hanem M. Awad; Howaida I. Abd-Alla; Khaled H. Mahmoud; Sayed A. El-Toumy (Medicinal Chemistry Research, 2014)

Novel Method for Determination of Anthracene by Coupling Dispersive Liquid-Liquid Extraction to First-Derivative Synchronous Spectrofluorimetry - Omar Abdel-Aziz; A. M. El Kosasy; Sherif Mahmoud El-Sayed Okeil (Journal of Fluorescence, 2014)

Vulnerability risk assessment and adaptation to climate change induced sea level rise along the Mediterranean coast of Egypt - Omran E. Frihy; Mahmoud Kh. El-Sayed (Mitigation and Adaptation Strategies for Global Change, 2013)

Novel PCU cage diol peptides as potential targets against wild-type CSA HIV-1 protease: synthesis, biological screening and molecular modelling studies - Rajshekhar Karpoormath; Yasien Sayed; Thavendran Govender; Hendrik G. Kruger; Mahmoud E. S. Soliman; Glenn E. M. Maguire (Medicinal Chemistry Research, 2013)

Earthquake-induced pounding between equal height multi-storey buildings considering soil-structure interaction - Sayed Mahmoud; Ayman Abd-Elhamed; Robert Jankowski (Bulletin of Earthquake Engineering, 2013)

Trace and REE element geochemistry of fluorite and its relation to uranium mineralizations, Gabal Gattar Area, Northern Eastern Desert, Egypt - Nasser Mourad Mahdy; Mahmoud Hany Shalaby; Hassan Mohamed Helmy; Ali Farage Osman; El Sayed H. El Sawey; Ehab Korany Abu Zeid (Arabian Journal of Geosciences, 2013)

Development of Artificial Seed Technology and Preservation in Sugar Beet - Aida A. Rizkalla; Awatef M. Badr-Elden; Mahmoud El-Sayed Ottai; M. I. Nasr; Marwa N. M. Esmail (Sugar Tech, 2012)

Simulation of the response of base-isolated buildings under earthquake excitations considering soil flexibility - Sayed Mahmoud; Per-Erik Austrell; Robert Jankowski (Earthquake Engineering and Engineering Vibration, 2012)

Structure–cytotoxicity relationship of a novel series of miconazole-like compounds - Reza Yousefi; Ali Khalafi-Nezhad; Mohammad Navid Soltani Rad; Somayeh Behrouz; Farhad Panahi; Mansoore Esmaili; Sayed Mahmoud Ghaffari; Ali Niazi; Ali Akbar Moosavi-Movahedi (Medicinal Chemistry Research, 2012)

Fenugreek attenuation of diabetic nephropathy in alloxan-diabetic rats - Ahmed Amir Radwan Sayed; Mahmoud Khalifa; Fathy Fahim Abd el-Latif (Journal of Physiology and Biochemistry, 2012)

New Luminescent Bioprobes Eu(lll)-phloroglucinol Derivatives and Their Spectrofluorimetric, Electrochemical Interactions with Nucleotides and DNA - Hassan Ahmed Azab; Zeinab M. Anwar; Enas T. Abdel-Salam; Mahmoud EL-Sayed-Sebak (Journal of Fluorescence, 2012)

Inhibition of melanogenesis by the extract from Agaricus blazei without affecting iNOS gene expression - Motamed Elsayed Mahmoud; Abd El-Latif Hesham; Yasser Abdel-Galil Ahmed; Mohammed Sayed (World Journal of Microbiology and Biotechnology, 2010)

Effects of ultraviolet A on the activity of two metabolic enzymes, DNA damage and lipid peroxidation during early developmental stages of the African catfish, Clarias gariepinus (Burchell, 1822) - Imam A. A. Mekkawy; Usama M. Mahmoud; Alaa G. Osman; Alaa El-Din H. Sayed (Fish Physiology and Biochemistry, 2010)

Characterization of NS3 protease from an Egyptian HCV genotype 4a isolate - Mahmoud Mohamed Bahgat; Ahmed Atef Ibrahim; Dina Nadeem Abd-Elshafy; Ahmed Atef Mesalam; Hossam Eid Gewaid; Amany Abd-Elghany Ismaeil; Ahmed Mohamed El-Waseef; Amany Sayed Maghraby; Ahmed Barakat Barakat; Mohamed Abd-Elhafez El-Far; Hossam El-Din Ahmed Ghanem; Amro Mahmoud Mohamed; et al. (Archives of Virology, 2009)

Fructose-amino acid conjugate and other constituents from Cyperus rotundus L. - Hanaa M. Sayed; Mahmoud H. Mohamed; Salwa F. Farag; Gamal A. Mohamed; Olanrewaju R.M. Omobuwajo; Peter Proksch (Natural Product Research, 2008)

A new steroid glycoside and furochromones from Cyperus rotundus L. - Hanaa M. Sayed; Mahmoud H. Mohamed; Salwa F. Farag; Gamal A. Mohamed; Peter proksch (Natural Product Research, 2007)

Impact of the cyclosporine-ketoconazole interaction in children with steroid-dependent idiopathic nephrotic syndrome - Amr El-Husseini; Fathy El-Basuony; Ihab Mahmoud; Ahmed Donia; Hussein Sheashaa; Alaa Sabry; Nabil Hassan; Nagy Sayed-Ahmad; Mohamed Sobh (European Journal of Clinical Pharmacology, 2006)

Mode of formation and sedimentary association of the reefal sediments, Ras Abu El Darag, Gulf of Suez, Egypt - Amr A. El-Sammak; Mahmoud Kh. El-Sayed; Mohammed A. El-Sabrouti (Carbonates and Evaporites, 2000)